Solid electrolyte material comprising a chalcogenide-based ion-conducting structure, in particular a sulfide-based ion-conducting structure

JP2024507170A5Pending Publication Date: 2025-02-20AMPCERA INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2023548811
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-02-11
Filing Date
2022-02-11
Publication Date
2025-02-20

AI Technical Summary

Technical Problem

Sulfide-based ionically conductive argyrodite structures in solid-state batteries face challenges such as metal dendrite penetration leading to short circuits and limited electrochemical window due to sulfur vacancies, which affect cell performance and energy density.

Method used

Incorporating an excess amount of sulfur or lithium sulfide into the argyrodite structure to form stuffed argyrodite structures, creating stacking faults that act as barriers to electron migration and enhance ionic conductivity, thereby stabilizing the electrolyte and increasing critical current density.

Benefits of technology

The stuffed argyrodite structures exhibit reduced electronic conductivity, higher critical current density, and improved chemical stability, leading to enhanced lithium dendrite suppression and longer cycle life of solid-state batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

A solid electrolyte material comprising a chalcogenide-based ion-conducting structure including one or more of lithium, sodium, aluminum, magnesium, iron, and potassium; one or more of sulfur, oxygen, selenium, and tellurium; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of an excess of chalcogen and an excess of chalcogenide incorporated in the chalcogenide-based ion-conducting structure.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 148,155, filed February 11, 2021, which is incorporated herein by reference in its entirety.

[0002] The present application relates to the field of solid state electrolyte materials. [Background technology]

[0003] Sulfide-based ion-conducting argyrodite structures are promising candidates for solid electrolyte materials for secondary batteries, especially solid-state batteries. However, sulfide-based ion-conducting argyrodite structures still face challenges. For example, metal dendrite growth can penetrate the sulfide-based ion-conducting argyrodite structures, leading to short circuits in the battery.

[0004] Therefore, those skilled in the art continue to conduct research and development in the field of solid electrolyte materials. Summary of the Invention [Means for solving the problem]

[0005] In one embodiment, the solid electrolyte material comprises a chalcogenide-based ion-conducting structure comprising one or more of lithium, sodium, aluminum, magnesium, iron, and potassium; one or more of sulfur, oxygen, selenium, and tellurium; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of an excess chalcogen and an excess chalcogenide incorporated into the chalcogenide-based ion-conducting structure.

[0006] In another embodiment, the solid electrolyte material comprises a sulfide-based ion-conducting structure comprising lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of excess sulfur and excess lithium sulfide incorporated into the sulfide-based ion-conducting structure.

[0007] In yet another embodiment, the solid electrolyte material comprises lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; one or more halogens; and a sulfide-based ion-conducting argyrodite structure comprising an excess amount of sulfur incorporated into the sulfide-based ion-conducting argyrodite structure.

[0008] In yet another embodiment, the solid electrolyte material comprises a sulfide-based ion-conducting argyrodite structure comprising lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; one or more halogens; and an excess of lithium sulfide incorporated into the sulfide-based ion-conducting argyrodite structure.

[0009] Other embodiments of the solid electrolyte material of the present disclosure will become apparent from the following detailed description, the accompanying drawings, and the appended claims. [Brief explanation of the drawings]

[0010] [Figure 1A] FIG. 1 shows the X-ray diffraction pattern for the stuffed sulfide-based ion-conducting argyrodite structure herein. [Figure 1B] FIG. 1 shows the X-ray diffraction pattern for a nominal stoichiometric sulfide-based ion-conducting argyrodite. [Figure 2]1 is a graph showing Hebb-Wagner polarization curves for stuffed argyrodite and nominal stoichiometric argyrodite. [Figure 3A] 1 is a graph showing symmetric lithium-lithium cycling curves for stuffed argyrodite formulations. [Figure 3B] 1 is a graph showing a symmetric lithium-lithium cycling curve for nominal stoichiometric argyrodite formation. [Figure 4] 1A and 1B are schematic diagrams of a standard unit cell and a unit cell with a stacking fault layer. [Figure 5] 1A and 1B are schematic diagrams of two adjacent standard unit cells and two adjacent standard unit cells with stacking faults. [Figure 6] 1A and 1B are schematic diagrams of two adjacent standard unit cells and two adjacent standard unit cells with stacking faults. [Figure 7] 1A and 1B are schematic diagrams of a standard unit cell and a unit cell with stacking faults. [Figure 8] 1A and 1B are schematic diagrams of two adjacent standard unit cells and two adjacent standard unit cells with stacking faults. [Figure 9] 1A and 1B are schematic diagrams of two adjacent standard unit cells and two adjacent standard unit cells with stacking faults. [Figure 10] FIG. 1 is a schematic diagram of a solid-state battery using the stuffed argyrodite herein as a solid electrolyte layer. [Figure 11] FIG. 1 is a schematic diagram of a solid-state lithium metal battery using the stuffed argyrodite herein as a solid electrolyte layer. [Figure 12] FIG. 1 is a schematic diagram of an anodeless solid-state battery using the stuffed argyrodite herein as a solid electrolyte layer. DETAILED DESCRIPTION OF THE INVENTION

[0011] Sulfide-based ion-conducting argyrodite structures are potential candidates for solid electrolyte materials for secondary batteries, particularly solid-state batteries. However, sulfide-based ion-conducting argyrodite structures still have challenges. For example, sulfur vacancies can increase the electronic conductivity of the argyrodite structure, leading to the growth of metal dendrites that can penetrate the argyrodite structure and lead to short circuits in the battery. Sulfur vacancies can also limit the electrochemical window of batteries using argyrodite as an electrolyte, limiting energy density. Battery performance can be enhanced by filling sulfur vacancies in argyrodite with excess sulfur. This specification addresses these and other challenges, providing chalcogenide- and sulfide-based ion-conducting structures that result in improved solid electrolyte materials.

[0012] The present specification relates to a solid electrolyte material comprising a chalcogenide-based ion-conducting structure that includes one or more of lithium, sodium, aluminum, magnesium, iron, and potassium; one or more of sulfur, oxygen, selenium, and tellurium; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of an excess of chalcogen and an excess of chalcogenide incorporated into the chalcogenide-based ion-conducting structure, forming what is referred to as a stuffed structure.

[0013] Typically, chalcogenide-based ion-conducting structures have one of the reactive metal ions lithium, sodium, aluminum, magnesium, iron, and potassium. In a preferred example, the chalcogenide-based ion-conducting structure has the reactive metal ion lithium. In a preferred example, the chalcogenide-based ion-conducting structure may be sulfide-based, having sulfur alone or in combination with oxygen, selenium, and tellurium.

[0014] The present specification also relates to a solid electrolyte material comprising a sulfide-based ion-conducting structure that includes lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of excess sulfur and excess lithium sulfide incorporated into the sulfide-based ion-conducting structure, forming what is called a stuffed structure. The sulfide-based ion-conducting structure may have only sulfur or sulfur in combination with oxygen, selenium, and tellurium.

[0015] In some embodiments, the chalcogenide- or sulfide-based ion-conducting structure may comprise one of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic. In other embodiments, the chalcogenide- or sulfide-based ion-conducting structure may comprise two of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic. In other embodiments, the chalcogenide- or sulfide-based ion-conducting structure may comprise three or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic.

[0016] In chalcogenide-based ion-conducting structures, the excess chalcogen may be sulfur, oxygen, selenium, tellurium, or a combination thereof. In a preferred example, the excess chalcogen is excess sulfur. The excess chalcogen or excess sulfur herein is incorporated into the chalcogenide-based or sulfide-based ion-conducting structure, as opposed to being a mixture with the chalcogenide-based or sulfide-based ion-conducting structure. In some embodiments, the excess chalcogen or excess sulfur may be incorporated into the structure in the form of defects disposed within the structure. Additionally or alternatively, the excess chalcogen or excess sulfur may be incorporated into the structure in the form of interstitials disposed within the structure. Additionally or alternatively, the excess chalcogen or excess sulfur may be incorporated into the structure in the form of superlattice stacking faults within the structure.

[0017] In the chalcogenide-based ion-conducting structure, the excess chalcogenide may be a chalcogenide of one or more of lithium, sodium, aluminum, magnesium, iron, and potassium with one or more of sulfur, oxygen, selenium, and tellurium. In one example, the chalcogenide is lithium with one or more of sulfur, oxygen, selenium, and tellurium. In another example, the chalcogenide is one or more of lithium, sodium, aluminum, magnesium, iron, and potassium with sulfur. In a preferred example, the chalcogenide is lithium sulfide.

[0018] The excess chalcogenide or excess lithium sulfide herein is incorporated into a chalcogenide-based or sulfide-based ion-conducting structure, as opposed to being a mixture with the chalcogenide-based or sulfide-based ion-conducting structure. In one embodiment, the excess chalcogenide or excess lithium sulfide may be incorporated into the structure in the form of a chalcogenide or lithium sulfide layer within the structure. In another embodiment, the excess chalcogenide or excess lithium sulfide may be present in the form of superlattice stacking faults in multiple chalcogenide or lithium sulfide layers within the structure. Chalcogenide-based or sulfide-based ion-conducting structures can be characterized by having a visible (111) peak in an X-ray diffraction pattern corresponding to the excess chalcogenide or excess lithium sulfide. Alternatively, such structures can be observed using a transmission electron microscope (TEM) or a high-resolution transmission electron microscope (HRTEM).

[0019] In certain embodiments, at least one of an excess amount of chalcogen (e.g., sulfur) and an excess amount of chalcogenide (e.g., lithium sulfide) incorporated into a chalcogenide-based (e.g., sulfide-based) ion-conducting structure can decrease the electronic conductivity of the chalcogenide-based ion-conducting structure, as shown in Figure 2. In certain embodiments, at least one of an excess amount of chalcogen (e.g., sulfur) and an excess amount of chalcogenide (e.g., lithium sulfide) incorporated into a chalcogenide-based ion-conducting structure can increase the critical current density of the chalcogenide-based ion-conducting structure, as shown in Figure 3. While not being limited by theory herein, it is believed that the decrease in electronic conductivity and / or the increase in critical current density can be attributed to excess chalcogenide (e.g., lithium sulfide) or excess chalcogen (e.g., sulfur) stacking faults in the chalcogenide-based (e.g., sulfide-based) ion-conducting structure. In the case of an excess amount of chalcogenide (e.g., lithium sulfide), one or more chalcogenide (e.g., lithium sulfide) stacking faults can serve as a barrier layer to prevent electron transport through the bulk material. In the case of an excess amount of chalcogen (e.g., sulfur), one or more vacant chalcogenide (e.g., lithium sulfide) stacking faults, combined with the low electronic conductivity of the chalcogen (e.g., sulfur), can limit electron transport through the bulk material. However, other mechanisms for reduced electronic conductivity and / or increased critical current density may additionally or alternatively exist. In another aspect, at least one of an excess amount of chalcogen (e.g., sulfur) and an excess amount of chalcogenide (e.g., lithium sulfide) incorporated into a chalcogenide-based ion-conducting structure may increase chemical stability with lithium metal (or sodium metal, aluminum metal, magnesium metal, iron metal, or potassium metal), which may be a contributing factor to the enhanced critical current density. In the case of excess amounts of both chalcogenide (e.g., lithium sulfide) and chalcogen (e.g., sulfur), the excess material can form a passivating layer on the lithium metal surface, resulting in the formation of a more stable solid electrolyte interfacial layer.In yet another aspect, lower electronic conductivity and higher critical current density may enhance the ability of chalcogenide-based ionically conductive structures to suppress lithium (or sodium, aluminum, magnesium, iron, or potassium) dendrites, enabling longer cycle life for solid-state metal batteries.

[0020] In some embodiments, chalcogenide-based (e.g., sulfide-based) ion-conducting structures having at least one of an excess amount of chalcogen (e.g., sulfur) and an excess amount of chalcogenide (e.g., lithium sulfide) can be compared to nominal stoichiometric chalcogenide-based (e.g., sulfide-based) ion-conducting structures that do not have at least one of an excess amount of chalcogen (e.g., sulfur) and an excess amount of chalcogenide (e.g., lithium sulfide). In certain embodiments, the electronic conductivity of the chalcogenide-based (e.g., sulfide-based) ion-conducting structures herein is less than the electronic conductivity of the nominal stoichiometric chalcogenide-based ion-conducting structures that do not have at least one of an excess amount of chalcogen and an excess amount of chalcogenide, preferably less than half, more preferably less than one-quarter of the electronic conductivity of the nominal stoichiometric chalcogenide-based ion-conducting structures. For example, the inventors herein have realized chalcogenide-based ion-conducting structures herein having electronic conductivity that is approximately one-tenth that of a nominal stoichiometric chalcogenide-based ion-conducting structure, as shown in Figure 2. In another aspect, the critical current density of a chalcogenide-based (e.g., sulfide-based) ion-conducting structure herein is higher, preferably at least 10% higher, more preferably at least 20% higher, more preferably at least 30% higher, and more preferably at least 40% higher, than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure that does not have at least one of an excess amount of chalcogen and an excess amount of chalcogenide. For example, the inventors herein have realized chalcogenide-based ion-conducting structures herein having critical current densities that are at least 40% higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure, as shown in Figure 3.

[0021] In some embodiments, the chalcogenide-based or sulfide-based ion-conducting structure may have an argyrodite structure or a non-argyrodite structure. The chalcogenide-based or sulfide-based ion-conducting non-argyrodite structure has a relatively high room temperature ionic conductivity (e.g., 10 -5 S / cm or greater) and preferably contains the elements lithium, sulfur, and phosphorus (or a mixture of phosphorus and non-phosphorus elements). Examples include thio-LISCON Li 10 GeP2S 12+n (where n corresponds to the excess sulfur, n>0). Another example is thio-LISCON Li 10+2n GeP2S 12+n where n corresponds to an excess of lithium sulfide, n>0. Additionally or alternatively, chalcogenide- or sulfide-based ion-conducting non-argyrodites contain the elements lithium, sulfur, phosphorus (or a mixture of phosphorus and non-phosphorus elements), and one or more halogens. Examples include Li 9.54 Si 1.74 P 1.44 S 11.7+n Cl 0.3 (where n corresponds to the excess sulfur, n>0). Another example is Li 9.54+2n Si 1.74 P 1.44 S 11.7+n Cl 0.3 where n corresponds to an excess of lithium sulfide and n>0. Other formulas for non-argyrodite structures incorporating excess chalcogen or excess chalcogenide will be apparent to those skilled in the art.

[0022] This specification also relates to a solid electrolyte material comprising a sulfide-based ion-conductive allodite structure containing sulfur combined with lithium; optionally oxygen, selenium, tellurium or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus and arsenic; one or more halogens; and an excess amount of sulfur incorporated into the sulfide-based ion-conductive allodite structure.

[0023] In one example, the sulfide-based ion-conductive allodite structure has the general formula: Li 12-m-x M m+ Y (6-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = optionally S combined with O 2- , Se 2- , Te 2- or a combination thereof; X 2- = F - , Cl - , Br - , I - or a combination thereof; x is in the range 0 ≦ x ≦ 2; n is in the range n > 0, preferably 0 < n ≦ 1).

[0024] In another example, the sulfide-based ion-conductive allodite structure has the general formula: Li 18-2m-x M2 m+ Y (9-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = optionally O​​2- 、 Se 2- 、 Te 2- or S combined with them 2- ; X - = F - 、 Cl - 、 Br - 、 I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2, and n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0025] In another example, a sulfide-based ion-conductive argyrodite structure has the general formula: Li 24-3m-x M3 m+ Y (12-x)+n X x (where M m+ = B 3+ 、 Ga 3+ 、 Sb 3+ 、 Si 4+ 、 Ge 4+ 、 Sn 4+ 、 P 5+ 、 As 5+ or a combination thereof; Y = optionally O 2- 、 Se 2- 、 Te 2- or S combined with them 2- ; X - = F - 、 Cl - 、 Br - 、 I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2, and n is greater than 0, preferably in the range of 0 < n ≦ 1) may also be included.

[0026] Other formulas for chalcogenide-based or sulfide-based ion-conductive argyrodite structures incorporating an excess amount of chalcogen or an excess amount of sulfur will be apparent to those skilled in the art.

[0027] This specification also relates to a solid electrolyte material comprising a sulfide-based ion-conductive allodite structure containing lithium; sulfur combined optionally with oxygen, selenium, tellurium or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus and arsenic; one or more halogens; and an excess amount of lithium sulfide incorporated into the sulfide-based ion-conductive allodite structure.

[0028] In one example, the sulfide-based ion-conductive allodite structure has the general formula: Li 12-m-x+2n M m+ Y (6-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = S optionally combined with O 2- , Se 2- , Te 2- or a combination thereof; X 2- = F - , Cl - , Br - , I - , or a combination thereof; x ranges from 0 ≦ x ≦ 2; n ranges from greater than 0, preferably 0 < n ≦ 20). - It may have.

[0029] In another example, the sulfide-based ion-conductive allodite structure has the general formula: Li 18-2m-x+2n M2 m+ Y (9-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+or combinations thereof; Y is optionally O 2- , Se 2- , Te 2- or S combined with combinations thereof 2- ; X - = F - , Cl - , Br - , I - or combinations thereof; x ranges from 0 ≦ x ≦ 2; n is greater than 0, preferably in the range 0 < n ≦ 20) may be had.

[0030] In another example, a sulfide-based ion-conductive argyrodite structure has the general formula: Li 24-3m-x+2n M3 m+ Y (12-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or combinations thereof; Y is optionally O 2- , Se 2- , Te 2- or S combined with combinations thereof 2- ; X - = F - , Cl - , Br - , I - or combinations thereof; x ranges from 0 ≦ x ≦ 2; n is greater than 0, preferably in the range 0 < n ≦ 20) may be had.

[0031] Other formulas for chalcogenide-based or sulfide-based ion-conductive argyrodite structures in which an excess of chalcogenide or an excess of lithium sulfide is incorporated into the structure will be apparent to those skilled in the art.

[0032] Throughout this specification, reference is made to sulfide-based ion-conducting argyrodite structures, but the principles herein apply to chalcogenide-based structures and non-argyrodite structures.

[0033] The argyrodite formulations herein may have lower electronic conductivity than argyrodite formulations having a nominal stoichiometric structure. Such a reduction in the electronic conductivity of the argyrodite is shown in the Hebb-Wagner polarization curve of FIG. 2.

[0034] The argyrodite formulations herein may have higher critical current densities than argyrodite formulations having nominal stoichiometric structures. Such enhanced critical current densities of the argyrodite formulations herein are shown in the symmetric lithium-lithium cycling curves of FIG.

[0035] The decrease in electronic conductivity and increase in critical current density can be attributed to an excess of LiS or an excess of sulfide stacking faults in the argyrodite crystal structure. In the case of an excess of LiS, one or more LiS stacking faults can serve as a barrier layer preventing electron transport through the bulk material. In the case of an excess of sulfide, one or more vacant lithium-sulfide stacking faults, in combination with the low electronic conductivity of sulfur, can limit electron transport through the bulk material.

[0036] The argyrodite formulations herein may have higher chemical stability with lithium metal than argyrodite formulations with nominal stoichiometric structures, which may be a contributing factor to the enhanced critical current density in Figure 3. In the case of excess amounts of both LiS and sulfide, the excess material may form a passivating layer on the lithium metal surface, resulting in a more stable solid electrolyte interfacial layer.

[0037] The combination of lower electronic conductivity and higher critical current density can enhance the lithium dendrite suppression capabilities of the argyrodite formulations herein over those of argyrodite formulations with nominal stoichiometric structures, enabling longer cycle life for solid-state lithium metal batteries.

[0038] In some embodiments, the electronic conductivity of the chalcogenide-based (e.g., sulfide-based) ion-conducting structures (argyrodite structures) herein is greater than 10 -7 S / cm or less, preferably 10 -8 S / cm or less, more preferably 10 -9 S / cm or less, more preferably 10 -10 In another embodiment, the critical current density of the chalcogenide-based (e.g., sulfide-based) ion-conducting structure is less than 0.2 mA / cm 2 More than 0.4 mA / cm 2 More preferably, greater than 0.6 mA / cm 2 More preferably, greater than 0.8 mA / cm 2 More preferably, greater than 1.0 mA / cm 2 More preferably, greater than 2.0 mA / cm 2 More preferably, greater than 3.0 mA / cm 2 More preferably, greater than 4.0 mA / cm 2 More preferably, greater than 5.0 mA / cm 2 It's super.

[0039] FIG. 1A is an X-ray diffraction pattern for a stuffed sulfide-based ion-conducting argyrodite structure herein. FIG. 1B is an X-ray diffraction pattern for a nominal stoichiometric sulfide-based ion-conducting argyrodite. FIG. 1A shows a single lithium sulfide peak at 27° corresponding to the (111)-lithium sulfide peak. The single lithium sulfide peak further indicates the integration of lithium sulfide in the form of superlattice stacking faults, as opposed to an excess of precursor, where multiple lithium sulfide peaks would be expected. Alternatively, such structures can be observed using transmission electron microscopy (TEM) or high-resolution transmission electron microscopy (HRTEM).

[0040] Figure 2: Hebb-Wagner polarization curves at a constant voltage of 0.3 V showing an order of magnitude reduction in electronic conductivity for the stuffed argyrodite (bottom of Figure 2) formulation herein over that of a nominal stoichiometric sulfide-based ionically conductive argyrodite (i.e., standard argyrodite formulation) (top of Figure 2). Evaluations were performed using 250 mg of solid electrolyte material (0.1 mm thick) in a PEEK split cell (1.13 cm 2 ) at room temperature under a pressure of 330 MPa. -8 and 4.4 × 10 -7 Electronic conductivity values ​​in S / cm were recorded for the stuffed argyrodite and the standard or nominal stoichiometric argyrodite formulations, respectively.

[0041] Figures 3A and 3B: Symmetric lithium-lithium cycling curves for (Figure 3A) the stuffed argyrodite formulation and (Figure 3B) its nominal stoichiometric argyrodite formation. Evaluations were performed using a lithium / magnesium alloy electrode at room temperature under a pressure of 20 MPa. The stuffed argyrodite formulation exceeded the critical current density (0.7 mA / cm) of its nominal stoichiometric argyrodite formulation. 2 ) and enhanced critical current density (1mA / cm 2 ) was shown.

[0042] Figure 4: General formula Li7-x PS 6-x Cl x Schematic diagram of a standard argyrodite unit cell (2) with A being the phosphorus-sulfur (PS) plane, B being the lithium-sulfide (Li-S) plane, and C being the phosphorus-sulfur-lithium-chloride (PS-Li-Cl) plane. An excess of lithium-sulfur (Li-S) stacking fault layer (B*) is formed between the B and C planes using high temperature and / or high pressure treatment (4), and has the general formula Li 9-x PS 7-x Cl x It is possible to form stuffed argyrodites having the general formula Li 7-x+2n PS 6-x+n Cl x The material may further include superlattice-like stacking faults containing two or more lithium-sulfur (Li-S) stacking fault layers (B**) formed between the B and C planes, with the formula: where n is the number of stacking fault layers within the unit cell. (6) Alternatively, one or more Li-S stacking fault layers may be formed between the A and B planes. In yet another alternative, one or more Li-S stacking fault layers may be formed both between the A and B planes and between the B and C planes.

[0043] In an alternative example, FIG. 4 shows a compound of general formula Li 10 MP2S 12 A unit cell (2) of a thio-LISCON solid electrolyte can be represented as follows: where A is a phosphorus mixed metal-sulfur ((P / M)-S) plane (where M can be Si, Ge, Sn, As, etc.), B is a lithium-sulfur (Li-S) plane, and C is a metal-phosphorus-sulfur-lithium (MPS-Li) plane. An excess lithium-sulfur (Li-S) stacking fault layer (B*) is formed between the B and C planes using high temperature and / or high pressure treatment (4), and has the general formula Li 12 MP2S 13 Stuffed thio-LISCONs can be formed having the general formula Li 10+2n MP2S 12+nwhere n is the number of stacking fault layers within the unit cell.

[0044] Figure 5: General formula Li 7-x PS 6-x Cl x Schematic diagram of two adjacent unit cells (i and ii) of standard argyrodite (8) with the general formula Li* (where A is the phosphorus-sulfur (PS) plane, B is the lithium-sulfide (Li-S) plane, and C is the phosphorus-sulfur-lithium-chloride (PS-Li-Cl) plane). An excess lithium-sulfur (Li-S) stacking fault layer (B*) is formed between the C plane of unit cell i and the A plane of unit cell ii using high temperature and / or high pressure treatment (10). 9-x PS 7-x Cl x It is possible to form stuffed argyrodites having the general formula Li 7-x+2n PS 6-x+n Cl x (where n is the number of stacking fault layers between the unit cells), and may further include superlattice-like stacking faults containing two or more lithium-sulfur (Li-S) stacking fault layers (B**) formed between the C-plane of unit cell i and the A-plane of unit cell ii (12).

[0045] In an alternative embodiment, FIG. 5 shows a compound of general formula Li 10 MP2S 12 A thio-LISCON solid electrolyte unit cell (8) can be shown having the general formula: where A is a phosphorus mixed metal-sulfur ((P / M)-S) plane (where M can be Si, Ge, Sn, As, etc.), B is a lithium-sulfur (Li-S) plane, and C is a metal-phosphorus-sulfur-lithium (MPS-Li) plane. An excess lithium-sulfur (Li-S) stacking fault layer (B*) is formed between the C plane of unit cell i and the A plane of unit cell ii using high temperature and / or high pressure treatment (10), and the thio-LISCON solid electrolyte unit cell (8) can be shown to have the general formula: 12 MP2S 13Stuffed thio-LISCONs can be formed having the general formula Li 10+2n MP2S 12+n (where n is the number of stacking fault layers between the unit cells), and may further include superlattice-like stacking faults containing two or more lithium-sulfur (Li-S) stacking fault layers (B**) formed between the C-plane of unit cell i and the A-plane of unit cell ii (12).

[0046] Figure 6: General formula Li 7-x PS 6-x Cl x Schematic diagram of two adjacent unit cells (i and ii) of standard argyrodite (8) with the general formula Li* (where A is the phosphorus-sulfur (PS) plane, B is the lithium-sulfide (Li-S) plane, and C is the phosphorus-sulfur-lithium-chloride (PS-Li-Cl) plane). Excessive lithium-sulfur (Li-S) stacking fault layers (B*) are formed between the A and B planes of both unit cells and between the C plane of unit cell i and the A plane of unit cell ii using high-temperature and / or high-pressure treatment (14). 9-x PS 7-x Cl x It is possible to form stuffed argyrodites having the general formula Li 7-x+2n PS 6-x+n Cl x The structure may further include superlattice-like stacking faults containing two or more lithium-sulfur (Li-S) stacking fault layers (B**) formed between the A and B planes of both unit cells and between the C plane of unit cell i and the A plane of unit cell ii, with the formula: (16) where n is the number of stacking fault layers within and between the unit cells. Alternatively, one or more Li-S stacking fault layers may be formed between the B and C planes of both unit cells and between the C plane of unit cell i and the A plane of unit cell ii. In another alternative, one or more Li-S stacking fault layers may be formed between both the A and B planes and the B and C planes of both unit cells, and between the C plane of unit cell i and the A plane of unit cell ii.

[0047] In an alternative example, FIG. 6 shows a compound of general formula Li 10 MP2S 12 where A is a phosphorus mixed metal-sulfur ((P / M)-S) plane (where M can be Si, Ge, Sn, As, etc.), B is a lithium-sulfur (Li-S) plane, and C is a metal-phosphorus-sulfur-lithium (MPS-Li) plane. Excessive lithium-sulfur (Li-S) stacking fault layers (B*) are formed between the A and B planes of both unit cells and between the C plane of unit cell i and the A plane of unit cell ii using high temperature and / or high pressure treatment (14), and the thio-LISCON solid electrolyte unit cell (8) has the general formula Li 12 MP2S 13 Stuffed thio-LISCONs can be formed having the general formula Li 10+2n MP2S 12+n where n is the number of stacking fault layers within and between the unit cells, and may further include superlattice-like stacking faults containing two or more lithium-sulfur (Li-S) stacking fault layers (B**) formed between the A and B planes of both unit cells and between the C plane of unit cell i and the A plane of unit cell ii (16).

[0048] Figure 7: General formula Li 7-x PS 6-x Cl x Schematic diagram of a standard argyrodite unit cell (2) with vacant lithium-sulfur (V) and vacant lithium-sulfur (V). Li -S) stacking fault layers (V*) are formed between the B and C planes using high temperature and / or high pressure treatments (18) and have the general formula Li 7-x PS 7-x Cl x It is possible to form stuffed argyrodites having the general formula Li 7-x PS 6-x+n Cl xwhere n is the number of stacking fault layers within the unit cell. Li -S) may further comprise a superlattice-like stacking fault containing stacking fault layer (V**) (20). Alternatively, one or more V Li A -S stacking fault layer may be formed between the A and B planes. In yet another alternative, one or more V Li The -S stacking fault layer may form both between the A and B planes and between the B and C planes.

[0049] In an alternative example, FIG. 7 shows a compound of general formula Li 10 MP2S 12 The figure shows a unit cell (2) of a thio-LISCON solid electrolyte having a phosphorus mixed metal-sulfur ((P / M)-S) plane (where M can be Si, Ge, Sn, As, etc.), B is a lithium-sulfur (Li-S) plane, and C is a metal-phosphorus-sulfur-lithium (MPS-Li) plane. Li -S) stacking fault layers (V*) are formed between the B and C planes using high temperature and / or high pressure treatments (18) and are of the general formula Li 10 MP2S 13 Stuffed thio-LISCONs can be formed having the general formula Li 10 MP2S 12+n where n is the number of stacking fault layers within the unit cell. Li -S) may further comprise a superlattice-like stacking fault containing stacking fault layer (V**) (20).

[0050] Figure 8: General formula Li 7-x PS 6-x Cl x Schematic diagram of two adjacent unit cells (i and ii) (8) of a standard argyrodite with vacant lithium-sulfur (V) planes (where A is the phosphorus-sulfur (PS) plane, B is the lithium-sulfide (Li-S) plane, and C is the phosphorus-sulfur-lithium-chloride (PS-Li-Cl) plane). Li-S) A stacking fault layer (V*) is formed between the C-plane of unit cell i and the A-plane of unit cell ii using high temperature and / or high pressure treatment (22), and has the general formula Li 7-x PS 7-x Cl x It is possible to form stuffed argyrodites having the general formula Li 7-x PS 6-x+n Cl x where n is the number of stacking fault layers between the unit cells. Li -S) may further include superlattice-like stacking faults containing stacking fault layers (V**) (24).

[0051] In an alternative embodiment, FIG. 8 shows a compound of general formula Li 10 MP2S 12 The figure shows a unit cell (8) of a thio-LISCON solid electrolyte having a phosphorus mixed metal-sulfur ((P / M)-S) plane (where M can be Si, Ge, Sn, As, etc.), B is a lithium-sulfur (Li-S) plane, and C is a metal-phosphorus-sulfur-lithium (MPS-Li) plane. Li -S) A stacking fault layer (V*) is formed between the C-plane of unit cell i and the A-plane of unit cell ii using high temperature and / or high pressure treatment (22), and has the general formula Li 10 MP2S 13 Stuffed thio-LISCONs can be formed having the general formula Li 10 MP2S 12+n where n is the number of stacking fault layers between the unit cells. Li -S) may further include superlattice-like stacking faults containing stacking fault layers (V**) (24).

[0052] Figure 9: General formula Li 7-x PS 6-x Cl xSchematic diagram of two adjacent unit cells (i and ii) (8) of a standard argyrodite with vacant lithium-sulfur (V) planes (where A is the phosphorus-sulfur (PS) plane, B is the lithium-sulfide (Li-S) plane, and C is the phosphorus-sulfur-lithium-chloride (PS-Li-Cl) plane). Li -S) stacking fault layers (V*) are formed between the A and B planes of both unit cells and between the C plane of unit cell i and the A plane of unit cell ii using high temperature and / or high pressure treatments (26), and are represented by the general formula Li 7-x PS 7-x Cl x It is possible to form stuffed argyrodites having the general formula Li 7-x PS 6-x+n Cl x where n is the total number of stacking fault layers within and between unit cells. Two or more vacant lithium-sulfur (V Li -S) may further comprise a superlattice-like stacking fault containing stacking fault layer (V**) (28). Alternatively, one or more V Li The -S stacking fault layer may form between the B and C planes of both unit cells, and between the C plane of unit cell i and the A plane of unit cell ii. Li A −S stacking fault layer may form between the A and B planes and between the B and C planes of both unit cells, and between the C plane of unit cell i and the A plane of unit cell ii.

[0053] In an alternative embodiment, FIG. 9 shows a compound of general formula Li 10 MP2S 12 The figure shows a unit cell (8) of a thio-LISCON solid electrolyte having a phosphorus mixed metal-sulfur ((P / M)-S) plane (where M can be Si, Ge, Sn, As, etc.), B is a lithium-sulfur (Li-S) plane, and C is a metal-phosphorus-sulfur-lithium (MPS-Li) plane. Li-S) stacking fault layers (V*) are formed using high temperature and / or high pressure treatments in the A and B planes of both unit cells, and between the C plane of unit cell i and the A plane of unit cell ii (26), and are represented by the general formula Li 10 MP2S 13 Stuffed thio-LISCONs can be formed having the general formula Li 10 MP2S 12+n where n is the total number of stacking fault layers within and between unit cells. Two or more vacant lithium-sulfur (V Li -S) may further comprise a superlattice-like stacking fault containing stacking fault layer (V**) (28).

[0054] Figure 10: Schematic diagram of a solid-state battery using stuffed argyrodite as a solid electrolyte layer (30), which separates a composite cathode layer (32) formed on a positive current collector (34) and a composite anode layer (36) formed on a negative current collector (38). The composite cathode layer (32) may contain the stuffed argyrodite in the form of a catholyte. The composite anode layer (36) may contain the stuffed argyrodite in the form of an anolyte.

[0055] Figure 11: Schematic diagram of a solid-state lithium metal battery using stuffed argyrodite as a solid electrolyte layer (30) separating a composite cathode layer (32) formed on a positive current collector (34) from a lithium metal anode layer (40) formed on a negative current collector (38). The composite cathode layer (32) may contain stuffed argyrodite in the form of a catholyte.

[0056] Figure 12: Schematic diagram of an anodeless solid-state battery using stuffed argyrodite as a solid electrolyte layer (30), which separates a composite cathode layer (32) formed on a positive current collector (34) from a negative current collector (38). The composite cathode layer (32) may contain stuffed argyrodite in the form of a catholyte.

[0057] Further details regarding the structures herein and methods for making and using the structures herein are described below: While the detailed description below focuses primarily on argyrodite structures having excess sulfur or excess lithium sulfide, the principles apply to non-argyrodite structures and structures having excess chalcogens other than sulfur or excess chalcogenides other than lithium sulfide.

[0058] In the case of excess sulfur, this can be achieved by treating argyrodite with high vapor pressures of sulfur or hydrogen sulfide (HS) at high temperatures. The excess sulfur can be used to fill sulfur vacancies, form interstitial sulfur, or form superlattice stacking faults. Superlattice stacking faults can be formed by a mixture of sulfur-lithium superlattice and sulfur-lithium defect pairs.

[0059] In the case of an excess amount of lithium sulfide, the excess can be achieved by adding additional lithium sulfide to the argyrodite composition. The excess amount of lithium sulfide can form superlattice stacking faults in one or more LiS layers. The superlattice stacking faults can be formed using high pressure and / or high temperature treatment.

[0060] Sulfur-stuffed argyrodite may decrease the electronic conductivity of the argyrodite, widen the electrochemical window of secondary batteries using argyrodite as an electrolyte, or increase the ionic conductivity of the argyrodite.

[0061] Argyrodite-structured solid electrolytes are advantageous in secondary batteries, especially solid-state batteries, due to their high room-temperature ionic conductivity. However, sulfur deficiencies can increase the electronic conductivity of argyrodite, leading to the growth of metallic dendrites that can penetrate and lead to short circuits in the battery. Sulfur deficiencies can also limit the electrochemical window of batteries using argyrodite as the electrolyte, limiting energy density. Battery performance can be enhanced by filling the sulfur deficiencies in argyrodite with excess sulfur.

[0062] In one embodiment, the argyrodite solid electrolyte material has the general formula: Li 12-m-x (M m+ Y4 2- )Y 2-x 2- X x - or Li 18-2m-x (M2 m+ Y7 2- )Y 2-x 2- X x- (In the formula, M m+ =B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y 2- =S 2- and in some cases, O 2- , Se 2- , Te 2- or a combination thereof; X - =F - , Cl - , Br - , I - or a combination thereof; x is in the range of 0≦x≦2).

[0063] In another embodiment, excess sulfur may be incorporated into the argyrodite material to form a sulfur-stuffed argyrodite structure. In one aspect, the excess sulfur can be used to fill sulfur vacancies in the argyrodite to form a sulfur-stuffed argyrodite. In another aspect, the excess sulfur can be used to form interstitial sulfur in the argyrodite to form a sulfur-stuffed argyrodite.

[0064] In yet another embodiment, excess sulfur can be used to form superlattice stacking faults in the argyrodite structure to form sulfur stuffed argyrodite. The superlattice stacking faults can be formed by sulfur-lithium defect pairs with a sulfur-lithium superlattice.

[0065] In yet another embodiment, sulfur-stuffed argyrodite with excess sulfur can appear in an X-ray diffraction pattern as a single (111) peak corresponding to LiS, which is the close-packed plane of lithium and sulfur atoms. Alternatively, such a structure can be observed using transmission electron microscopy (TEM) or high-resolution transmission electron microscopy (HRTEM).

[0066] In yet another embodiment, a high pressure processing method can be used to increase the sulfur or hydrogen sulfide (HS) vapor pressure and force excess sulfur into the argyrodite to form a sulfur-stuffed argyrodite.

[0067] In yet another embodiment, a high temperature treatment method can be used to force excess elemental sulfur into argyrodite to form sulfur-stuffed argyrodite.

[0068] In yet another embodiment, the sulfur-stuffed argyrodite structure with excess sulfur has the general formula: Li 12-m-x M m+ Y (6-x)+n X x or Li 18-2m-x M2m+ Y (9-x)+n X x (where M m+ =B 3+ 、Ga 3+ 、Sb 3+ 、Si 4+ 、Ge 4+ 、Sn 4+ 、P 5+ 、As 5+ or a combination thereof; Y = S 2- and in some cases, O 2- 、Se 2- 、Te 2- or a combination with a combination thereof may be; X - = F - 、Cl - 、Br - 、I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2, and n is greater than 0, preferably in the range of 0 < n ≦ 1).

[0069] In one embodiment, an alditol doped with sulfur by an excess amount of sulfur may have an alditol composition consisting of phosphorus and one or more halogens.

[0070] In another embodiment, an alditol doped with sulfur by an excess amount of sulfur may have an alditol composition consisting of a phosphorus mixture and one or more halogens.

[0071] In yet another embodiment, an alditol doped with sulfur by an excess amount of sulfur may have an alditol composition consisting of a non - phosphorus element and one or more halogens.

[0072] In yet another embodiment, an alditol doped with sulfur by an excess amount of sulfur may have an alditol composition consisting of a non - phosphorus mixture and one or more halogens.

[0073] In yet another embodiment, an excess amount of lithium sulfide may be integrated into the alditol material, and an alditol structure doped with sulfur is formed.

[0074] In certain embodiments, an excess amount of lithium sulfide may be incorporated into the argyrodite material, which may form superlattice stacking faults in one or more of the Li2S layers.

[0075] In some embodiments, the planes of superlattice stacking faults may appear in an X-ray diffraction pattern as a single (111) peak corresponding to LiS, which is a close-packed plane of lithium and sulfur atoms. Alternatively, such structures can be observed using transmission electron microscopy (TEM) or high-resolution transmission electron microscopy (HRTEM).

[0076] In another embodiment, a high pressure treatment method can be used to increase the lithium sulfide vapor pressure and force excess lithium sulfide into the argyrodite structure.

[0077] In yet another embodiment, a high temperature treatment method can be used to force excess lithium sulfide into the argyrodite structure.

[0078] In yet another embodiment, the argyrodite structure, sulfur-stuffed with excess lithium sulfide, has the general formula: Li 12-m-x+2n M m+ Y (6-x)+n X x or Li 18-2m-x+2n M2 m+ Y (9-x)+n X x (In the formula, M m+ =B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y=S 2- and in some cases, O 2- , Se 2- , Te 2- or a combination thereof; X - =F - , Cl- , Br - , I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2; n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0079] In one aspect, the sulfur-stuffed alditol with an excess amount of lithium sulfide may have an alditol formulation consisting of phosphorus and one or more halogens.

[0080] In another aspect, the sulfur-stuffed alditol with an excess amount of lithium sulfide may have an alditol formulation consisting of a phosphorus mixture and one or more halogens.

[0081] In still another aspect, the sulfur-stuffed alditol with an excess amount of lithium sulfide may have an alditol formulation consisting of a non-phosphorus element and one or more halogens.

[0082] In still another aspect, the sulfur-stuffed alditol with an excess amount of lithium sulfide may have an alditol formulation consisting of a non-phosphorus mixture and one or more halogens.

[0083] In still another embodiment, the sulfur-stuffed alditol can be used to enhance the performance of a secondary battery, particularly a solid battery.

[0084] In one aspect, the sulfur-stuffed alditol can be used to reduce the electronic conductivity of a solid electrolyte.

[0085] In another aspect, the sulfur-stuffed alditol can be used to increase the ionic conductivity of a solid electrolyte.

[0086] [[ID=3�]] In yet another aspect, sulfur-stuffed argyrodites can be used to expand the electrochemical performance window of secondary batteries that use argyrodites as solid electrolytes.

[0087] In yet another embodiment, sulfur-stuffed argyrodites can be used to enhance the chemical compatibility of argyrodites with active cathode materials and other materials in secondary batteries.

[0088] In yet another embodiment, sulfur-stuffed argyrodite can be used to block lithium dendrite penetration, enhancing secondary battery cycle life.

[0089] In yet another aspect, sulfur-stuffed argyrodite can be used to enhance the critical current density of solid electrolytes, thus increasing the power rate of solid-state secondary batteries.

[0090] The present disclosure relates to solid electrolyte materials.

[0091] The solid electrolyte may include or be formed from a solid, ionically conductive material, which may be described as a material that may have the following characteristics:

[0092] Solid ionically conductive materials are a class of materials that can selectively pass certain charged elements in the presence of an electric field or chemical potential, such as a concentration difference.

[0093] This solid, ionically conductive material allows ions to move through it, but electrons cannot pass through it easily.

[0094] The ions may have one, two, three, four or more positive charges. Examples of charged ions include, for example, H + , Li + , Na + , K. + , Ag + , Mg 2+ , Zn2+ , Al 3+ , Fe 3+ etc.

[0095] The ionic conductivity of the corresponding ions is preferably 10 -7 S / cm. Lower electronic conductivity (10 -7 It is preferable that the surface roughness is less than 1 / 2 S / cm.

[0096] Solid ionically conductive materials include, for example, those having the general formula: Li 12-m-x (M m+ Y4 2- )Y 2-x 2- X x - or Li 18-2m-x (M2 m+ Y7 2- )Y 2-x 2- X x- [a) In the formula, M m+ contains boron (B 3+ ), Gallium (Ga 3+ ), aluminum (Al 3+ ), antimony (Sb 3+ ), silicon (Si 4+ ), germanium (Ge 4+ ), Phosphorus (P 5+ ), arsenic (As 5+ ) or a combination thereof. b) In the formula, Y 2- is sulfur (S 2- ), and in some cases other nonmetallic chalcogen elements, such as oxygen (O 2- ), selenium (Se 2- ), Tellurium (Te 2- ) or combinations thereof. c) In the formula, X - is a halogen, e.g., fluorine (F - ), chlorine (Cl - ), bromide (Br - ), iodine (I - ) or a combination thereof, where x is in the range of 0≦x≦2. The argyrodite material may be included.

[0097] This disclosure relates to the treatment of sulfur-stuffed aludidite with an excessive amount of sulfur.

[0098] The synthesis of sulfur-stuffed aludidite may include, for example, a solid-phase reaction in which an excessive amount of elemental sulfur is added to a ceramic powder mixture before the synthesis to form sulfur-stuffed aludidite.

[0099] The synthesis of sulfur-stuffed aludidite may include, for example, a solution-based reaction in which an excessive amount of elemental sulfur is added to a solution before the synthesis to form sulfur-stuffed aludidite.

[0100] The synthesis of sulfur-stuffed aludidite may include, for example, a solvent-based reaction in which an excessive amount of elemental sulfur is added to a solvent-based solution before the synthesis to form sulfur-stuffed aludidite.

[0101] The synthesis of sulfur-stuffed aludidite may include, for example, increasing the sulfur vapor pressure by high pressure in a sealed synthesis vessel to put or push an excessive amount of sulfur into the aludidite structure to form sulfur-stuffed aludidite.

[0102] The synthesis of sulfur-stuffed aludidite may include, for example, increasing the hydrogen sulfide vapor pressure by high pressure in a sealed synthesis vessel to put or push an excessive amount of sulfur into the aludidite structure to form sulfur-stuffed aludidite.

[0103] The vapor pressure may be in the range of 1 < p ≤ 100 atm.

[0104] The synthesis of sulfur-stuffed aludidite may include, for example, putting or pushing an excessive amount of sulfur into the aludidite structure by high temperature to form sulfur-stuffed aludidite.

[0105] The temperature may be in the range of 100 ≦ T ≦ 1000 °C.

[0106] The synthesis of sulfur-stuffed alldidite can have parameters sufficient to integrate an excess amount of sulfur into the alldidite structure to form sulfur-stuffed alldidite.

[0107] Using any synthesis method not disclosed, sulfur-stuffed alldidite can be formed using an excess amount of sulfur, where the parameters of the synthesis method are sufficient to incorporate or push an excess amount of sulfur into the alldidite structure to form sulfur-stuffed alldidite.

[0108] This disclosure relates to compositions of sulfur-stuffed alldidite with an excess amount of sulfur.

[0109] [[ID=​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​ Aldirodite stuffed with sulfur by an excess amount of sulfur may contain, for example, a composition of aldirodite containing phosphorus and a single halogen having the formula: Li 7-x PS (6-x)+n X x (where X is a halogen element and x is in the range of 0 ≦ x ≦ 2). The formulation may contain, for example, Li6PS 5+n Cl, Li 6.25 PS 5.25+n Br 0.75 、Li 5.75 PS 4.75+n I 1.25 etc. (where n is greater than 0, preferably in the range of 0 < n ≦ 1).

[0111] Aldirodite stuffed with sulfur by an excess amount of sulfur may contain, for example, a composition of aldirodite containing phosphorus and two or more halogens having the formula: Li 7-x’-x’’ PS (6-x’-x’’)+n X’ x’ X’’ x’’ (where X’ and X’’ are two different halogen elements and x’ + x’’ ≦ 2). The formulation may contain, for example, Li6PS 5+n Cl 0.5 Br 0.5 、Li 5.75 PS 4.75+n Cl 0.75 I 0.5 、Li 6.25 PS 5.25+n I 0.5 Br 0.25 etc. (where n is greater than 0, preferably in the range of 0 < n ≦ 1).

[0112] Aldirodite stuffed with sulfur by an excess amount of sulfur may contain, for example, a composition of aldirodite having the formula: Li 12-((5+m) / 2)-x M y m+ P 1-y S (6-x)+n X x (where M m+is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2), and an alditol composition containing a phosphorus mixture and a single halogen may be included. The formulation may include, for example, Li7Sb y P 1-y S 5+n Cl, Li 6.5 Si y P 1-y S 5+n Br, Li6Sn y P 1-y S 4.5+n Cl 1.5 , Li6As y P 1-y S 5+n I, etc. (where y is in the range of 0.001 ≦ y ≦ 0.999, and n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0113] In alditol stuffed with sulfur by an excess amount of sulfur, for example, the formula: Li 12-((5+m) / 2)-x’-x’’ M y m+ P 1-y S (6-x’-x’’)+n X’ x’ X’’ x’’ (where X’ and X’’ are two different halogens, and x’ + x’’ ≦ 2), and an alditol composition containing a phosphorus mixture and two or more halogens may be included. The formulation may include, for example, Li7B y P 1-y S 5+n Cl 0.5 Br 0.5 , Li 6.75 Sb y P 1-y S 4.75+n Cl 0.5 I 0.75 , Li6Si y P 1-y S 4.5+n Cl 0.75 Br 0.75 , Li 6.5 Sn y P 1-y S 5+n Br 0.5 I 0.5etc. (where y is in the range of 0.001 ≦ y ≦ 0.999 and n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0114] Aldirodite stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 12-m-x M m+ S (6-x)+n X x (where M m+ is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2), a single non-phosphorus aldirite composition containing a single halogen may be included. The formulation may include, for example, Li8BS 5+n Cl, Li 7.5 SbS 4.5+n Br 1.5 , Li7SiS 5+n I, Li 7.25 SnS 5.25+n Cl 0.75 , Li 5.75 AsS 4.75+n Br 1.25 etc. (n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0115] Aldirodite stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 12-m-x’-x’’ M m+ S (6-x’-x’’)+n X’ x’ X’’ x’’ (M m+ is a positively charged ion other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≦ 2), a single non-phosphorus aldirite composition containing two or more halogens may be included. The formulation may include, for example, Li8SbS 5+n Cl 0.5 Br 0.5 , Li 6.75 SiS 4.75+n Cl 0.75 Br 0.5 , Li7SnS 5+n Cl 0.5 Br 0.5 , Li 5.5 AsS 4.5+n Br0.75 I 0.75 etc. (where n is greater than 0, preferably in the range of 0 < n ≤ 1) may be included.

[0116] Alditolates stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 12-((m’+m’’) / 2)-x M y m’ M 1-y m’’ S (6-x)+n X x (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X is a halogen element, and x is in the range of 0 ≤ x ≤ 2), an alditolate composition containing a non - phosphorus mixture and a single halogen may be included. The formulation may include, for example, Li8B y Sb 1-y S 5+n Cl, Li 7.2 Sb y Si 1-y S 4.7+n Br 1.3 、Li 7.25 Si y Sn 1-y S 5.25+n I 0.75 、Li 6.5 B y As 1-y S 4.5+n Cl 1.5 、Li 6.25 Si y As 1-y S 4.75+n Br 1.25 etc. (where y is in the range of 0.001 ≤ y ≤ 0.999, and n is greater than 0, preferably in the range of 0 < n ≤ 1) may be included.

[0117] Alditolates stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 12-((m’+m’’) / 2)-x’-x’’ M y m’ M 1-y m’’ S (6-x’-x’’)+n X’ x’ X’’ x’’ (where M m’and M m’’ are two different positively charged ions other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≤ 2), and an alditol composition having the following formula containing a non-phosphorus mixture and two or more halogens may be included. For the formulation, for example, Li8Ga y Sb 1-y S 5+n Cl 0.5 Br 0.5 、Li 7.25 Sb y Si 1-y S 4.75+n Cl 0.75 Br 0.5 、Li7Si y Ge 1-y S 5+n Cl 0.5 I 0.5 、Li 6.85 Sn y Si 1-y S 4.85+n Cl 0.7 I 0.45 、Li6As y Sn 1-y S 4.5+n I 0.75 Br 0.75 (where y is in the range of 0.001 ≤ y ≤ 0.999, and n is greater than 0, preferably in the range of 0 < n ≤ 1) may be included.

[0118] An alditol stuffed with sulfur by an excess amount of sulfur integrated into the alditol structure has the general formula: Li 18-2m-x M2 m+ Y (9-x)+n X x (where M m+ = B 3+ 、Ga 3+ 、Sb 3+ 、Si 4+ 、Ge 4+ 、Sn 4+ 、P 5+ 、As 5+ or a combination thereof; Y = S 2- and in some cases, O 2- 、Se 2- 、Te 2-Or a combination with combinations thereof; X - = F - , Cl - , Br - , I - Or a combination thereof; x is in the range of 0 ≦ x ≦ 2; n is greater than 0, preferably in the range of 0 < n ≦ 1) May have

[0119] In alditolite stuffed with sulfur by an excess amount of sulfur, for example, the formula: Li 8-x P2S (9-x)+n X x (In the formula, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2), an alditolite composition containing phosphorus and a single halogen may be included. In the formulation, for example, Li7P2S 8+n Cl, Li 7.25 P2S 8.25+n Br 0.75 ​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​ Aldirodite stuffed with sulfur by an excess amount of sulfur contains, for example, a formula: Li 18-(5+m)-x M y m+ P 2-y S (9-x)+n X<U+ x (where M m+ is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2), an Aldirodite composition containing a phosphorus mixture and a single halogen may be included. The formulation may include, for example, Li9Sb y P 2-y S 8+n Cl, Li8Si y P 2-y S 8+n Br, Li 7.5 Sn y P 2-y S 7.5+n Cl 1.5 、Li7As y P 2-y S 8+n I, etc. (where y is in the range of 0.001 ≦ y ≦ 1.999, and n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0122] Aldirodite stuffed with sulfur by an excess amount of sulfur contains, for example, a formula: Li 18-(5+m)-x’-x’’ M y m+ P 2-y S (9-x’-x’’)+n X’ x’ X’’ x’’ (where X’ and X’’ are two different halogens, and x’ + x’’ ≦ 2), an Aldirodite composition containing a phosphorus mixture and two or more halogens may be included. The formulation may include, for example, Li9B y P 2-y S 8+n Cl 0.5 Br 0.5 、Li 8.75 Sb y P<U+ 2-y S 7.75+n Cl 0.5 I 0.75 、Li 7.5 Si yP 2-y S 3.5+n Cl 0.75 Br 0.75 、Li8Sn y P 2-y S 8+n Br 0.5 I 0.5 etc. (where y is in the range of 0.001 ≦ y ≦ 1.999 and n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0123] Aldirodite stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 18-2m-x M2 m+ S (9-x)+n X x (where M m+ is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2), a single non - phosphorus aldirodite composition containing a single halogen may be included. The formulation may include, for example, Li 11 B2S 8+n Cl, Li 10.5 Sb2S 7.5+n Br 1.5 、Li9Si2S 8+n I、Li 9.25 Sn2S 8.25+n Cl 0.75 、Li 6.75 As2S 7.75+n Br 1.25 etc. (where n is greater than 0, preferably in the range of 0 < n ≦ 1) may be included.

[0124] Aldirodite stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 18-2m-x’-x’’ M2 m+ S (9-x’-x’’)+n X’ x’ X’’ x’’ (where M m+ is a positively charged ion other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≦ 2), a single non - phosphorus aldirodite composition containing two or more halogens may be included. The formulation may include, for example, Li 11 Sb2S 8+n Cl0.5 Br 0.5 、Li 8.75 Si2S 7.75+n Cl 0.75 Br 0.5 、Li9Sn2S 8+n Cl 0.5 Br 0.5 、Li 6.5 As2S 7.5+n Br 0.75 I 0.75 etc. (where n is greater than 0, preferably in the range of 0 < n ≤ 1) may be included.

[0125] Aldirodite stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 18-(m’+m’’)-x M y m’ M 2-y m’’ S (9-x)+n X x (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X is a halogen element, and x is in the range of 0 ≤ x ≤ 2), an aldirodite composition containing a non-phosphorus mixture and a single halogen may be included. The formulation may include, for example, Li 11 B y Sb 2-y S 8+n Cl, Li 9.7 Sb y Si 2-y S<000075​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​ Aldirodite stuffed with sulfur by an excess amount of sulfur may include, for example, the formula: Li 18-(m’+m’’)-x’-x’’ M y m’ M 2-y m’’ S (9-x’-x’’)+n X’ x’ X’’ x’’ (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≤ 2), and an aldirodite composition containing a non - phosphorus mixture and two or more halogens may be included. The formulation may include, for example, Li 11 Ga y Sb 2-y S 8+n Cl 0.5 Br 0.5 、Li 9.75 Sb y ​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​​The synthesis of sulfur - stuffed alunite may involve, for example, a solid - state reaction in which an excess amount of lithium sulfide is added to a ceramic powder mixture prior to the synthesis to form sulfur - stuffed alunite.

[0129] The synthesis of sulfur - stuffed alunite may involve, for example, a solution - based reaction in which an excess amount of lithium sulfide is added to a solution prior to the synthesis to form sulfur - stuffed alunite.

[0130] The synthesis of sulfur - stuffed alunite may involve, for example, a solvent - based reaction in which an excess amount of lithium sulfide is added to a solvent - based solution prior to the synthesis to form sulfur - stuffed alunite.

[0131] The synthesis of sulfur - stuffed alunite may involve, for example, increasing the lithium sulfide vapor pressure by high pressure in a sealed synthesis vessel to incorporate or push an excess amount of lithium sulfide into the alunite structure to form sulfur - stuffed alunite.

[0132] The vapor pressure may be in the range of 1 < p ≤ 1000 atm.

[0133] The synthesis of sulfur - stuffed alunite may involve, for example, incorporating or pushing an excess amount of lithium sulfide into the alunite structure by high temperature to form sulfur - stuffed alunite.

[0134] The temperature may be in the range of 100 ≤ T ≤ 1000 °C.

[0135] The synthesis of sulfur - stuffed alunite can have parameters sufficient to integrate an excess amount of lithium sulfide into the alunite structure to form sulfur - stuffed alunite.

[0136] Using any synthetic method not disclosed, it is possible to form sulfur-stuffed al-dirodite using an excess amount of lithium sulfide. At this time, the parameters of the synthetic method are sufficient to incorporate or push an excess amount of lithium sulfide into the al-dirodite structure to form sulfur-stuffed al-dirodite.

[0137] This disclosure relates to a composition of sulfur-stuffed al-dirodite with an excess amount of lithium sulfide.

[0138] An excess amount of lithium sulfide can form superlattice stacking defects in one or more Li2S layers in the al-dirodite structure, and sulfur-stuffed al-dirodite is formed.

[0139] The sulfur-stuffed al-dirodite integrated into the al-dirodite structure by an excess amount of lithium sulfide has the following general formula: Li 12-m-x+2n M m+ Y (6-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = S 2- and in some cases may be a combination with O 2- , Se 2- , Te 2- or a combination thereof, and X - = F - , Cl - , Br - , I - or a combination thereof; x ranges from 0 ≦ x ≦ 2, and n is greater than 0, preferably in the range 0 < n ≦ 20) may have.

[0140] The sulfur-stuffed al-dirodite with an excess amount of lithium sulfide has, for example, the formula: Li7-x+2n PS (6-x)+n X x (where X is a halogen element and x ranges from 0 ≦ x ≦ 2), an alditol composition containing phosphorus and a single halogen may be included. In the formulation, for example, Li 6+2n PS〖JP09000000A〗 5+n Cl, Li 6.25+2n PS 5.25+n Br 0.75 , Li 5.75+2n PS 4.75+n I 1.25 etc. (where n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0141] In alditol stuffed with lithium sulfide by an excessive amount of sulfur, for example, the formula: Li 7-x’-x’’+2n PS (6-x’-x’’)+n X’ x’ X’’ x’’ (where X’ and X’’ are two different halogen elements and x’ + x’’ ≦ 2), an alditol composition containing phosphorus and two or more halogens may be included. In the formulation, for example, Li 6+2n PS 5+n Cl 0.5 Br 0.5 , Li 5.75+2n [〖JP09000000A〗]PS[[ID=

[46] ] 4.75+n Cl 0.75 I 0.5 , Li 6.25+2n PS 5.25+n I 0.5 Br 0.25 etc. (where n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0142] In alditol stuffed with an excessive amount of lithium sulfide, for example, the formula: Li 12-((5+m) / 2)-x+2n M y m+ P 1-y S (6-x)+n X x (where M m+is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2), and an alditol composition containing a phosphorus mixture and a single halogen may be included. The formulation may include, for example, Li 7+2n Sb y P 1-y S 5+n Cl, Li 6.5+2n Si y P 1-y S 5+n Br, Li<Q000872>Sn y P 1-y S 4.5+n Cl 1.5 , Li 6+2n As y P 1-y S 5+n I, etc. (where y is in the range of 0.001 ≦ y ≦ 0.999 and n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0143] In alditol stuffed with sulfur by an excessive amount of lithium sulfide, for example, the formula: Li 12-((5+m) / 2)-x’-x’’+2n M y m+ P 1-y S (6-x’-x’’)+n X’ x’ X’’ x’’ (where X’ and X’’ are two different halogens and x’ + x’’ ≦ 2), and an alditol composition containing a phosphorus mixture and two or more halogens may be included. The formulation may include, for example, Li 7+2n B y P 1-y S 5+n Cl 0.5 Br 0.5 , Li 6.75+2n Sb y P 1-y S 4.75+n Cl 0.5 I 0.75 , Li 6+2n Si y P 1-y S 4.5+n Cl 0.75 Br 0.75 , Li 6.5+2n Sn y P 1-y S5+n Br 0.5 I 0.5 etc. (where y is in the range of 0.001 ≦ y ≦ 0.999, and n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0144] In the case of argyrodite stuffed with sulfur by an excessive amount of lithium sulfide, for example, a single non-phosphorus argyrodite composition having the formula: Li 12-m-x+2n M m+ S (6-x)+n X x (where M m+ is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0 ≦ x ≦ 2) may be included. The formulation may include, for example, Li 8+2n BS 5+n Cl, Li 7.5+2n SbS 4.5+n Br 1.5 , Li 7+2n SiS 5+n I, Li 7.25+2n SnS 5.25+n Cl 0.75 , Li 5.75+2n AsS 4.75+n Br 1.25 etc. (where n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0145] In the case of argyrodite stuffed with sulfur by an excessive amount of lithium sulfide, for example, a single non-phosphorus argyrodite composition having the formula: Li 12-m-x’-x’’+2n M m+ S (6-x’-x’’)+n X’ x’ X’’ x’’ (M m+ is a positively charged ion other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≦ 2) may be included. The formulation may include, for example, Li 8+2n SbS 5+n Cl 0.5 Br 0.5 , Li 6.75+2n SiS 4.75+n Cl 0.75 Br0.5 , Li 7+2n SnS 5+n Cl 0.5 Br 0.5 , Li 5.5+2n AsS 4.5+n Br 0.75 I 0.75 etc. (where n is greater than 0, preferably in the range 0 < n ≤ 20) may be included.

[0146] Aldirodite stuffed with sulfur by an excess amount of lithium sulfide may include, for example, the formula: Li 12-((m’+m’’) / 2)-x+2n M y m’ M 1-y m’’ S (6-x)+n X x (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X is a halogen element, and x is in the range 0 ≤ x ≤ 2), an aldirodite composition containing a non - phosphorus mixture and a single halogen may be included. The formulation may include, for example, Li 8+2n B y Sb 1-y S 5+n Cl, Li 7.2+2n Sb y Si 1-y S 4.7+n Br 1.3 , Li 7.25+2n Si y Sn 1-y S 5.25+n I 0.75 , Li 6.5+2n B y As 1-y S 4.5+n Cl 1.5 , Li 6.25+2n Si y As 1-y S 4.75+n Br 1.25 etc. (where y is in the range 0.001 ≤ y ≤ 0.999, and n is greater than 0, preferably in the range 0 < n ≤ 20) may be included.

[0147] Aldirodite stuffed with sulfur by an excess amount of lithium sulfide may include, for example, the formula: Li12-((m’+m’’) / 2)-x’-x’’+2n M y m’ M 1-y m’’ S (6-x’-x’’)+n X’ x’ X’’ x’’ (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≤ 2), a non-phosphorus mixture and an aludidite composition containing two or more halogens may be included. The formulation may include, for example, Li 8+2n Ga y Sb 1-y S 5+n Cl 0.5 Br 0.5 , Li 7.25+2n Sb y Si 1-y S 4.75+n Cl 0.75 Br 0.5 , Li 7+2n Si y Ge 1-y S 5+n Cl 0.5 I 0.5 , Li 6.85+2n Sn y Si 1-y S 4.85+n Cl 0.7 I 0.45 , Li 6+2n As y Sn 1-y S 4.5+n I 0.75 Br 0.75 (where y is in the range of 0.001 ≤ y ≤ 0.999 and n is greater than 0, preferably in the range of 0 < n ≤ 20) may be included.

[0148] The aludidite stuffed with sulfur by an excess amount of lithium sulfide integrated into the aludidite structure has the general formula: Li 18-2m-x+2n M2 m+ Y (9-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+, Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = S 2- and in some cases, O 2- , Se 2- , Te 2- or a combination with a combination thereof may be; X - = F - , Cl - , Br - , I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2, and n is in the range of greater than 0, preferably 0 < n ≦ 20) may have

[0149] Iodadite stuffed with sulfur by an excess amount of lithium sulfide may include, for example, a formula: Li 8-x+2n P2S (9-x)+n X x (where X is a halogen element and x is in the range of 0 ≦ x ≦ 2), and an iodadite composition containing phosphorus and a single halogen may be included. The formulation may include, for example, Li 7+2n P2S 8+n Cl, Li 7.25+2n P2S 8.25+n Br 0.75 , Li 6.75+2n P2S 7.75+n I 1.25 etc. (where n is in the range of greater than 0, preferably 0 < n ≦ 20) may be included.

[0150] Iodadite stuffed with sulfur by an excess amount of lithium sulfide may include, for example, a formula: Li 8-x’-x’’+2n P2S (9-x’-x’’)+n X’ x’ X’’ x’’ (where X’ and X’’ are two different halogen elements and x’ + x’’ ≦ 2), and an iodadite composition containing phosphorus and two or more halogens may be included. The formulation may include, for example, Li 7+2n P2S 8+n Cl 0.5 Br 0.5, Li 6.75+2n P2S 7.75+n Cl 0.75 I 0.5 , Li 7.25+2n P2S 8.25+n I 0.5 Br 0.25 etc. (where n is greater than 0, preferably in the range 0 < n ≤ 20) may be included.

[0151] In the case of al-dilithium sulfide in which sulfur is doped with an excess amount of lithium sulfide, for example, the formula: Li 18-(5+m)-x+2n M y m+ P 2-y S (9-x)+n X x (where M m+ is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range 0 ≤ x ≤ 2) may include an al-dilithium sulfide composition containing a phosphorus mixture and a single halogen. In the formulation, for example, Li 9+2n Sb y P 2-y S 8+n ]>Cl, Li 8+2n Si y P 2-y S 8+n Br, Li 7.5+2n Sn y P 2-y S 7.5+n Cl 1.5 , Li 7+2n As y P 2-y S 8+n I etc. (where y is in the range 0.001 ≤ y ≤ 1.999, and n is greater than 0, preferably in the range 0 < n ≤ 20) may be included.

[0152] [[ID=�3]]In the case of al-dilithium sulfide in which sulfur is doped with an excess amount of lithium sulfide, for example, the formula: Li 18-(5+m)-x’-x’’+2n M y m+ P 2-y S (9-x’-x’’)+n X’ x’ X’’ x’’(where X' and X'' are two different halogen elements, and x'+x''≤2), a phosphorus mixture and an aludidite composition containing two or more halogens may be included. In the formulation, for example, Li 9+2n B y P 2-y S 8+n Cl 0.5 Br 0.5 、Li 8.75+2n Sb y P 2-y S 7.75+n Cl 0.5 I 0.75 、Li 7.5+2n Si y P 2-y S 3.5+n Cl 0.75 Br 0.75 、Li 8+2n Sn y P 2-y S 8+n Br[[ID=!45]] 0.5 I 0.5 etc. (where y is in the range of 0.001≤y≤1.999, and n is greater than 0, preferably in the range of 0 < n≤20) may be included.

[0153] In the aludidite stuffed with sulfur by an excess amount of lithium sulfide, for example, the formula: Li 18-2m-x+2n M2 m+ S (9-x)+n X x (where M m+ is a positively charged ion other than phosphorus, X is a halogen element, and x is in the range of 0≤x≤2) having a single halogen-containing single non-phosphorus aludidite composition may be included. In the formulation, for example, Li 11+2n B2S 8+n Cl, Li 10.5+2n Sb2S 7.5+n Br 1.5 、Li 9+2n Si2S 8+n I、Li 9.25+2n Sn2S 8.25+n Cl 0.75 、Li 6.75+2n As2S 7.75+n Br 1.25 Note: There seems to be a potential error in the original text where the tag "!45" might be incorrect. It's left as is in the translation following the instruction to preserve all tags exactly.etc. (where n is greater than 0, preferably in the range of 0 < n ≤ 20) may be included.

[0154] In the case of al-djerosite stuffed with sulfur by an excessive amount of lithium sulfide, for example, the formula: Li 18-2m-x’-x’’+2n M2 m+ S (9-x’-x’’)+n X’ x’ X’’ x’’ (where M m+ is a positively charged ion other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≤ 2) having a single non-phosphorus al-djerosite composition containing two or more halogens may be included. In the formulation, for example, Li 11+2n Sb2S 8+n Cl 0.5 Br 0.5 、Li 8.75+2n Si2S 7.75+n Cl 0.75 Br 0.5 、Li 9+2n Sn2S 8+n Cl 0.5 Br 0.5 、Li 6.5+2n As2S 7.5+n Br 0.75 I 0.75 etc. (where n is greater than 0, preferably in the range of 0 < n ≤ 20) may be included.

[0155] In the case of al-djerosite stuffed with sulfur by an excessive amount of lithium sulfide, for example, the formula: Li 18-(m’+m’’)-x+2n M y m’ M 2-y m’’ S (9-x)+n X x (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X is a halogen element, and x is in the range of 0 ≤ x ≤ 2) having an al-djerosite composition containing a non-phosphorus mixture and a single halogen may be included. In the formulation, for example, Li 11+2n B y Sb 2-y S 8+n Cl, Li9.7+2n Sb y Si 2-y S 7.7+n Br 1.3 、Li 9.25+2n Si y Sn 2-y S 8.25+n I 0.75 、Li 8.5+2n B y As 2-y S 7.5+n Cl 1.5 、Li 7.75+2n Si y As 2-y S 7.75+n Br 1.25 etc. (where y is in the range of 0.001 ≦ y ≦ 1.999 and n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0156] In the case of sulfur-stuffed aludidite with an excessive amount of lithium sulfide, for example, the formula: Li 18-(m’+m’’)-x’-x’’+2n M y m’ M 2-y m’’ S (9-x’-x’’)+n X’ x’ X’’ x’’ (where M m’ and M m’’ are two different positively charged ions other than phosphorus, X’ and X’’ are two different halogen elements, and x’ + x’’ ≦ 2), a non-phosphorus mixture and an aludidite composition containing two or more halogens may be included. In the formulation, for example, Li 11+2n Ga y Sb 2-y S 8+n Cl 0.5 Br 0.5 、Li 9.75+2n Sb y Si 2-y S 7.75+n Cl 0.75 Br 0.5 、Li 9+2n Si y Ge 2-y S 8+n Cl 0.5 I 0.5 、Li 8.85+2n Sn ySi 2-y S 7.85+n Cl 0.7 I 0.45 、Li 7.5+2n As y Sn 2-y S 7.5+n I 0.75 Br 0.75 (where y is in the range of 0.001 ≦ y ≦ 1.999, and n is greater than 0, preferably in the range of 0 < n ≦ 20) may be included.

[0157] The present disclosure relates to the characteristics of sulfur-stuffed al-diludite.

[0158] An al-diludite formulation without sulfur stuffing or with a nominal stoichiometry can be defined as an al-diludite that does not contain an excess amount of sulfur or lithium sulfide.

[0159] The excess sulfur can be used to fill sulfur deficiencies in the al-diludite, and the sulfur-stuffed al-diludite has a smaller number of sulfur deficiencies than an al-diludite formulation without sulfur stuffing or with a nominal stoichiometry.

[0160] The excess sulfur can be used to form interlayer sulfur in the al-diludite, and the sulfur-stuffed al-diludite has more interlayer sulfur than an al-diludite formulation without sulfur stuffing or with a nominal stoichiometry.

[0161] The excess sulfur can be used to form superlattice stacking defects, which are formed by a mixture of sulfur-lithium regular lattices and sulfur-lithium defect pairs, and the sulfur-stuffed al-diludite has more sulfur-lithium lattices and sulfur-lithium defect pairs than an al-diludite formulation without sulfur stuffing or with a nominal stoichiometry.

[0162] Excess lithium sulfide can be used to form superlattice stacking faults in one or more LiS layers, and sulfur-stuffed argyrodite has more LiS layers in the form of superlattice stacking faults than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0163] Excessive amounts of sulfur or lithium sulfide can be used to reduce the electronic conductivity of the argyrodite, with sulfur-stuffed argyrodite having lower electronic conductivity than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0164] Excess sulfur or lithium sulfide can be used to increase the ionic conductivity of the argyrodite, with the sulfur-stuffed argyrodite having a higher ionic conductivity than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0165] Excess sulfur or lithium sulfide can be used to block lithium dendrite growth in secondary batteries, and secondary batteries using sulfur-stuffed argyrodite as a solid electrolyte have higher cycle life than secondary batteries using non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0166] Excess sulfur or lithium sulfide can be used to increase the critical current density of the argyrodite material, with the sulfur-stuffed argyrodite having a higher critical current density than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0167] Excess sulfur or lithium sulfide can be used to increase the power rate of secondary batteries, and secondary batteries using sulfur-stuffed argyrodite as a solid electrolyte have higher power rates than secondary batteries using non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0168] Excess sulfur or lithium sulfide can be used to widen the electrochemical window of secondary batteries, with secondary batteries using sulfur-stuffed argyrodite as the solid electrolyte having a wider electrochemical window than secondary batteries using non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0169] Secondary batteries can include, for example, solid-state batteries, hybrid solid-state batteries, semi-hybrid solid-state batteries, lithium metal batteries, hybrid lithium metal batteries, semi-hybrid lithium metal batteries, anodeless batteries, anodeless lithium metal batteries, hybrid anodeless lithium metal batteries, semi-hybrid anodeless lithium metal batteries, lithium-air batteries, lithium primary batteries, microbatteries, thin film batteries, lithium-sulfur batteries, and the like.

[0170] Excess sulfur or lithium sulfide can be used to widen the electrochemical window of the argyrodite, making the sulfur-stuffed argyrodite chemically compatible with the cathode material.

[0171] Cathode materials include, for example, layered YMO2, Y-rich layered Y 1+x M 1-x Examples of suitable oxides include O2, spinel-type YM2O4, olivine-type YMPO4, silicate-type Y2MSiO4, borate-type YMBO3, tavorite-type YMPO4F (wherein M is Fe, Co, Ni, Mn, Cu, Cr, etc.), (wherein Y is Li, Na, K, Mg, Zn, Al, etc.), vanadium oxide, sulfur, lithium sulfide, FeF3, and LiSe.

[0172] For lithium intercalation, cathode materials include, for example, lithium iron phosphate (LiFePO), lithium cobalt oxide (LiCoO), lithium manganese oxide (LiMnO), and lithium nickel oxide (LiNiO), lithium nickel cobalt manganese oxide (LiNi x Co y Mn zO2, 0.95≧x≧0.5, 0.3≧y≧0.025, 0.2≧z≧0.025), lithium nickel cobalt aluminum oxide (LiNi x Co y Al z O2, 0.95≧x≧0.5, 0.3≧y≧0.025, 0.2≧z≧0.025), lithium nickel manganese spinel (LiNi 0.5 Mn 1.5 O4) etc.

[0173] The cathode may be coated with a protective layer to prevent reaction between the sulfur-stuffed argyrodite, in which case high voltages are required but the electrochemical window is not significantly expanded. The protective layer may be composed of, for example, lithium borate, lithium aluminate (LiAlO), lithium tungstate (LiWO), lithium niobate (LiNbO), lithium phosphate (LiPO), lithium oxysulfide (LiAlSO, LiPO-LiS-SiS), lithium oxynitride (LiPON), etc.

[0174] The sulfur-stuffed argyrodite can be used in the cathode in the form of a catholyte to form a composite cathode. The sulfur-stuffed argyrodite may be mixed into a composite or milled with the active cathode material to form a core-shell structure, with the sulfur-stuffed argyrodite making up most, if not all, of the shell.

[0175] Sulfur-stuffed argyrodite can be used as a cathode in a lithium-sulfur battery, where the excess sulfur or lithium sulfide can serve as the active cathode material in the lithium-sulfur battery, with the remainder of the argyrodite structure serving as the catholyte, allowing for a dilute electrolyte.

[0176] Excess sulfur or lithium sulfide can be used to improve chemical compatibility with lithium metal or lithium metal alloy anodes, and sulfur-stuffed argyrodites have greater chemical stability with lithium metal or lithium metal alloy anodes than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations. Alloying metals can include, for example, indium, zinc, magnesium, manganese, etc.

[0177] Excess sulfur or lithium sulfide can be used to improve chemical compatibility with current collectors, such as copper, with sulfur-stuffed argyrodites being more chemically stable with current collectors than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0178] Excess sulfur or lithium sulfide can be used to improve chemical compatibility with carbon or electronically conductive additives, such as carbon black, making sulfur-stuffed argyrodites more chemically stable with electronically conductive additives than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0179] Excess sulfur or lithium sulfide can be used to improve chemical compatibility with anode materials, such as graphite or silicon, such that sulfur-stuffed argyrodites have greater chemical stability with anode materials than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0180] Excess sulfur or lithium sulfide can be used to improve chemical compatibility with liquid electrolytes, such as carbonate-based organic liquid electrolytes or room temperature ionic liquid electrolytes, such that sulfur-stuffed argyrodites have greater chemical stability with liquid electrolytes than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations.

[0181] Excess sulfur or lithium sulfide can be used to improve chemical compatibility with the heatable material embedded in the solid electrolyte, with sulfur-stuffed argyrodites being more chemically stable with the embedded heatable material than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations. The embedded material can be heated using resistance, induction, or dielectric heating methods.

[0182] Excess sulfur or lithium sulfide can be used to improve the chemical compatibility of the heatable material embedded in the solid electrolyte with the electronic insulating coating, with sulfur-stuffed argyrodite being more chemically stable with the insulating coating than non-sulfur-stuffed or nominal stoichiometric argyrodite formulations. The embedded material can be heated using resistance, induction, or dielectric heating methods.

[0183] The sulfur stuff argyrodite can be used in the form of an anolyte in the anode to form a composite anode.

[0184] The figures of the present disclosure further describe sulfur-stuffed argyrodite materials.

[0185] Figure 1: X-ray diffraction patterns for a) sulfur-stuffed argyrodite and b) non-sulfur-stuffed or nominal stoichiometric argyrodite formulations. The sulfur-stuffed argyrodite pattern shows a single lithium sulfide peak at 27° corresponding to the (111)-lithium sulfide peak. The single peak further indicates the integration of lithium sulfide in the form of superlattice stacking faults, as opposed to an excess of precursor, where multiple lithium sulfide peaks would be expected. Alternatively, such structures can be observed using transmission electron microscopy (TEM) or high-resolution transmission electron microscopy (HRTEM).

[0186] Figure 2: Hebb-Wagner polarization curves at a constant voltage of 0.3 V showing an order of magnitude decrease in electronic conductivity for the sulfur-stuffed argyrodite (bottom) formulation over that of the nominal stoichiometric (standard) argyrodite formulation (top). Evaluations were performed using 250 mg of solid electrolyte material (0.1 mm thick) in a PEEK split cell (1.13 cm 2 ) at room temperature under a pressure of 330 MPa. -8 and 4.4 × 10 -7 Electronic conductivity values ​​in S / cm were recorded for the sulfur-stuffed argyrodite and the standard or nominal stoichiometric argyrodite formulations, respectively.

[0187] The above systems and methods may be ascribed terms other than sulfur-stuffed argyrodite, such as sulfur-enriched argyrodite, sulfur-rich argyrodite, sulfur-sufficient argyrodite, sulfur-packed argyrodite, sulfur-filled argyrodite, sulfur-fortified argyrodite, and the like.

[0188] The above systems and methods can be attributed to argyrodite materials that include chalcogen elements other than sulfur, such as oxygen, selenium, tellurium, or combinations thereof. Such materials can be referred to as, for example, oxygen-stuffed argyrodite, selenium-stuffed argyrodite, or tellurium-stuffed argyrodite.

[0189] The above system and method does not have an argyrodite structure, but still has relatively high room temperature ionic conductivity (10 -5 S / cm or higher), which can be attributed to sulfide-based solid electrolyte materials containing elemental lithium and sulfur, and the chalcogenide-based or sulfide-based ion-conducting structures can have an argyrodite structure or a non-argyrodite structure. The chalcogenide-based or sulfide-based ion-conducting non-argyrodite structure has a relatively high room temperature ionic conductivity (e.g., 10 -5S / cm or greater) and preferably contains the elements lithium, sulfur, and phosphorus (or a mixture of phosphorus and non-phosphorus elements). Examples include thio-LISCON Li 10 GeP2S 12+n (where n corresponds to the excess sulfur, n>0). Another example is thio-LISCON Li 10+2n GeP2S 12+n where n corresponds to an excess of lithium sulfide, n>0. Additionally or alternatively, chalcogenide- or sulfide-based ion-conducting non-argyrodites contain the elements lithium, sulfur, phosphorus (or a mixture of phosphorus and non-phosphorus elements), and one or more halogens. Examples include Li 9.54 Si 1.74 P 1.44 S 11.7+n Cl 0.3 (where n corresponds to the excess sulfur, n>0). Another example is Li 9.54+2n Si 1.74 P 1.44 S 11.7+n Cl 0.3 (n corresponds to the excess of lithium sulfide, n>0). Other formulas will be apparent to those skilled in the art.

[0190] The above system and method is directed to argyrodite formulations, e.g., Li 24-3m-x (M3 m+ Y 10 2- )Y 2-x 2- X x (In the formula, M m+ =B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y=S 2- and in some cases, O 2- , Se 2- , Te 2- or a combination thereof; X - =F- , Cl - , Br - , I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2). Further, Li 24-3m-x M3 m+ S (12-x)+n X x and Li 24-3m-x+2n M3 m+ S (12-x)+n X x The formulations of and can each correspond to an excess amount of sulfur and an excess amount of lithium sulfide, where n > 0. Examples include Li8P3S 11+n Cl and Li 8+2n P3S 11+n Cl. The formulas of other argyrodites will be apparent to those skilled in the art.

[0191] The above systems and methods can be attributed to argyrodite materials stuffed with sulfur by a chemistry other than lithium ions, and this can include, for example, sodium ions, aluminum ions, magnesium ions, iron ions, potassium ions, etc.

[0192] The above systems and methods can be attributed to argyrodite powder or other forms stuffed with sulfur for commercial availability.

[0193] The above systems and methods can be attributed to argyrodite stuffed with sulfur in the form of, for example, powder, nanopowder, micropowder, composite, pellet, disk, plate, film, thin film, etc.

[0194] The above systems and methods can be attributed to ceramic-polymer composite solid electrolyte membranes, where the sulfur stuffed argyrodite is a ceramic material and the ceramic addition amount has a mass percentage in the range of 0.1 < p < 99.99%. The ceramic-polymer composite solid electrolyte may be supported on a cloth support.

[0195] The above system and method can be attributed to a solid electrolyte membrane comprised of sulfur-stuffed argyrodite, which membrane is formed using high-throughput processing techniques, such as cold spraying, supersonic particle deposition, thermal spraying, flame spraying, plasma spraying, etc. The membrane may be formed on a current collector, an anode, a composite anode, a lithium or metal alloy anode, a cathode, a composite cathode, etc. Processing can be carried out in air, under vacuum, or in an inert environment.

[0196] The above system and method can be attributed to a solid electrolyte membrane comprised of sulfur-stuffed argyrodite, which membrane is formed using physical high vacuum processing methods, such as pulsed laser deposition, sputtering, etc. The membrane may be formed on a current collector, an anode, a composite anode, a lithium or lithium metal alloy anode, a cathode, a composite cathode, etc.

[0197] The above systems and methods can be attributed to secondary batteries including, for example, solid state batteries, hybrid solid state batteries, semi-hybrid solid state batteries, lithium metal batteries, hybrid lithium metal batteries, semi-hybrid lithium metal batteries, anodeless batteries, anodeless lithium metal batteries, hybrid anodeless lithium metal batteries, semi-hybrid anodeless lithium metal batteries, lithium-air batteries, lithium primary batteries, microbatteries, thin film batteries, lithium-sulfur batteries, and the like.

[0198] The above system and method can be applied to a variety of secondary battery designs, such as pouch cells, coin cells, button cells, cylindrical cells, prismatic cells, and the like.

[0199] The above systems and methods can be attributed to secondary batteries having end use applications such as, for example, electric vehicles, hybrid electric vehicles, mobile devices, handheld electronics, household appliances, medical, medical wearables, and wearables for portable energy storage.

[0200] The above system and method can be attributed to secondary batteries for grid-scale energy storage backup systems.

[0201] The above systems and methods can be used in space, for example, at locations other than near-Earth, including space stations, both natural and artificial satellites, and planetary bodies such as Mars.

[0202] The above systems and methods can result in secondary batteries with longer life, higher energy and power densities, and improved safety.

[0203] The above system and method can be attributed to a redox flow or flow battery as the separator between the anolyte and catholyte.

[0204] The above system and method can be attributed to non-battery applications, such as upstream lithium mining or downstream spent battery recycling, where the sulfur-stuffed argyrodite is in the form of a dense membrane used to extract lithium from lithium containing solutions such as brine or spent battery effluent.

[0205] The above system and method can be attributed to the formation of sulfur-stuffed argyrodite onto a porous substrate, such as aluminum foam or nickel mesh, for either battery or non-battery applications.

[0206] The following items are included to highlight certain particular combinations of features herein, to which the invention herein is not limited.

[0207] 1. A solid electrolyte material comprising a chalcogenide-based ion-conducting structure including one or more of lithium, sodium, aluminum, magnesium, iron, and potassium; one or more of sulfur, oxygen, selenium, and tellurium; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of an excess amount of chalcogen and an excess amount of chalcogenide incorporated into the chalcogenide-based ion-conducting structure.

[0208] 2. The solid electrolyte material of item 1, wherein an excess amount of chalcogen is disposed within defects in the chalcogenide-based ion-conducting structure.

[0209] 3. The solid electrolyte material of any one of items 1-2, wherein an excess amount of chalcogen is located interstitially in the chalcogenide-based ion-conducting structure.

[0210] 4. The solid electrolyte material of any one of items 1 to 3, wherein the excess chalcogen is present in the form of superlattice stacking faults within the chalcogenide-based ion-conducting structure.

[0211] 5. The solid electrolyte material of any one of items 1 to 4, wherein the excess chalcogenide is present in the form of a chalcogenide layer within a chalcogenide-based ion-conducting structure.

[0212] 6. The solid electrolyte material of any one of items 1 to 5, wherein the excess amount of chalcogenide is present in the form of superlattice stacking faults in multiple chalcogenide layers within the chalcogenide-based ion-conducting structure.

[0213] 7. The solid electrolyte material of any one of items 1 to 6, wherein the chalcogenide-based ion-conducting structure has a visible (111) peak in the X-ray diffraction pattern corresponding to an excess amount of chalcogenide.

[0214] 8. The solid electrolyte material of any one of items 1 to 7, wherein the electronic conductivity of the chalcogenide-based ionically conductive structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is less than the electronic conductivity of a nominal stoichiometric chalcogenide-based ionically conductive structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0215] 9. The solid electrolyte material of any one of items 1 to 8, wherein the electronic conductivity of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is less than half the electronic conductivity of a nominal stoichiometric chalcogenide-based ion-conducting structure without at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0216] 10. The solid electrolyte material of any one of items 1 to 9, wherein the electronic conductivity of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is less than one-fourth the electronic conductivity of a nominal stoichiometric chalcogenide-based ion-conducting structure without at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0217] 11. The solid electrolyte material of any one of items 1 to 10, wherein the electronic conductivity of the chalcogenide-based ionically conductive structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is approximately one-tenth of the electronic conductivity of a nominal stoichiometric chalcogenide-based ionically conductive structure without at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0218] 12. The electronic conductivity of chalcogenide-based ionic conducting structures is 10 -7 12. The solid electrolyte material of any one of items 1 to 11, wherein the solid electrolyte material has a resistivity of less than 1000 kJ / cm.

[0219] 13. The electronic conductivity of chalcogenide-based ionic conducting structures is 10 -813. The solid electrolyte material of any one of items 1 to 12, wherein the solid electrolyte material has a resistivity of less than 1000 kJ / cm.

[0220] 14. The electronic conductivity of chalcogenide-based ionic conducting structures is 10 -9 14. The solid electrolyte material of any one of items 1 to 13, wherein the solid electrolyte material has a resistivity of less than 1000 kJ / cm.

[0221] 15. The electronic conductivity of chalcogenide-based ionic conducting structures is 10 -10 15. The solid electrolyte material of any one of items 1 to 14, wherein the solid electrolyte material has a resistivity of less than 1000 kJ / cm.

[0222] 16. The solid electrolyte material of any one of items 1 to 15, wherein the critical current density of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0223] 17. The solid electrolyte material of any one of items 1 to 16, wherein the critical current density of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is at least 10% higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0224] 18. The solid electrolyte material of any one of items 1 to 17, wherein the critical current density of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is at least 20% higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure without at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0225] 19. The solid electrolyte material of any one of items 1 to 18, wherein the critical current density of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is at least 30% higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure without at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0226] 20. The solid electrolyte material of any one of items 1 to 19, wherein the critical current density of the chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is at least 40% higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

[0227] 21. The critical current density of chalcogenide-based ion-conducting structures is 0.2 mA / cm 2 The solid electrolyte material of any one of items 1 to 20, which is ultra-

[0228] 22. The critical current density of chalcogenide-based ion-conducting structures is 0.4 mA / cm 2 22. The solid electrolyte material of any one of items 1 to 21, wherein the solid electrolyte material is ultra-

[0229] 23. The critical current density of chalcogenide-based ion-conducting structures is 0.6 mA / cm 2 23. The solid electrolyte material of any one of items 1 to 22, wherein the solid electrolyte material is ultra-

[0230] 24. The critical current density of chalcogenide-based ion-conducting structures is 0.8 mA / cm 2 24. The solid electrolyte material of any one of items 1 to 23, wherein the solid electrolyte material is ultra-

[0231] 25. The critical current density of a chalcogenide-based ion-conducting structure is 1.0 mA / cm 2 The solid electrolyte material of any one of items 1 to 24, wherein the solid electrolyte material is ultra-

[0232] 26. The critical current density of a chalcogenide-based ion-conducting structure is 2.0 mA / cm 2 The solid electrolyte material of any one of items 1 to 25, which is ultra-

[0233] 27. The critical current density of a chalcogenide-based ion-conducting structure is 3.0 mA / cm 2 27. The solid electrolyte material of any one of items 1 to 26, wherein the solid electrolyte material is ultra-

[0234] 28. The critical current density of a chalcogenide-based ion-conducting structure is 4.0 mA / cm 2 28. The solid electrolyte material of any one of items 1 to 27, wherein the solid electrolyte material is ultra-

[0235] 29. The critical current density of a chalcogenide-based ion-conducting structure is 5.0 mA / cm 2 29. The solid electrolyte material of any one of items 1 to 28, wherein the solid electrolyte material is ultra-

[0236] 30. The solid electrolyte material of any one of items 1 to 29, wherein the chalcogenide-based ion-conducting structure contains lithium.

[0237] 31. The solid electrolyte material of any one of items 1 to 30, wherein the chalcogenide-based ion-conducting structure contains sulfur.

[0238] 32. The solid electrolyte material of any one of items 1 to 31, wherein the chalcogenide-based ion-conducting structure contains phosphorus.

[0239] 33. The solid electrolyte material of any one of items 1 to 32, wherein the excess chalcogen comprises an excess amount of sulfur.

[0240] 34. The solid electrolyte material of any one of items 1 to 33, wherein the excess chalcogenide comprises an excess of lithium sulfide.

[0241] 35. The solid electrolyte material of any one of items 1 to 34, wherein the chalcogenide-based ion-conducting structure has an argyrodite structure.

[0242] 36. The solid electrolyte material of item 35, wherein the argyrodite structure has two or more halogens.

[0243] 37. A solid electrolyte material comprising a sulfide-based ion-conducting structure comprising lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and at least one of an excess of sulfur and an excess of lithium sulfide incorporated into the sulfide-based ion-conducting structure.

[0244] 38. The solid electrolyte material of item 37, wherein an excess amount of sulfur is disposed within defects in the sulfide-based ion-conducting structure.

[0245] 39. The solid electrolyte material of any one of items 37-38, wherein an excess amount of sulfur is located interstitially in the sulfide-based ion-conducting structure.

[0246] 40. The solid electrolyte material of any one of items 37 to 39, wherein the excess sulfur is present in the form of superlattice stacking faults within the sulfide-based ion-conducting structure.

[0247] 41. The solid electrolyte material of any one of items 37 to 40, wherein the excess lithium sulfide is present in the form of lithium sulfide layers within a sulfide-based ion-conducting structure.

[0248] 42. The solid electrolyte material of any one of items 37 to 41, wherein the excess lithium sulfide is present in the form of superlattice stacking faults in multiple lithium sulfide layers within the sulfide-based ion-conducting structure.

[0249] 43. The solid electrolyte material of any one of items 37 to 42, wherein the sulfide-based ion-conducting structure has a visible (111) peak in the X-ray diffraction pattern corresponding to an excess amount of chalcogenide.

[0250] 44. The solid electrolyte material of any one of items 37 to 43, wherein the electronic conductivity of the sulfide-based ionically conductive structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is less than the electronic conductivity of a nominal stoichiometric sulfide-based ionically conductive structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0251] 45. The solid electrolyte material of any one of items 37 to 44, wherein the electronic conductivity of the sulfide-based ionically conductive structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is less than half the electronic conductivity of a nominal stoichiometric sulfide-based ionically conductive structure without at least one of an excess amount of ion and an excess amount of lithium sulfide.

[0252] 46. ​​The solid electrolyte material of any one of items 37 to 45, wherein the electronic conductivity of the sulfide-based ionically conductive structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is less than one-fourth the electronic conductivity of a nominal stoichiometric sulfide-based ionically conductive structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0253] 47. The solid electrolyte material of any one of items 37 to 46, wherein the electronic conductivity of the sulfide-based ionically conductive structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is approximately one-tenth of the electronic conductivity of a nominal stoichiometric sulfide-based ionically conductive structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0254] 48. The electronic conductivity of sulfide-based ionic conductive structures is 10 -7 48. The solid electrolyte material of any one of items 37 to 47, having a resistivity of less than S / cm.

[0255] 49. The electronic conductivity of sulfide-based ionic conductive structures is 10 -8 49. The solid electrolyte material of any one of items 37 to 48, having a resistivity of less than S / cm.

[0256] 50. The electronic conductivity of sulfide-based ionic conductive structures is 10 -9 49. The solid electrolyte material of any one of items 37 to 49, having a resistivity of less than S / cm.

[0257] 51. The electronic conductivity of sulfide-based ionic conductive structures is 10 -10 51. The solid electrolyte material of any one of items 37 to 50, having a resistivity of less than S / cm.

[0258] 52. The solid electrolyte material of any one of items 37 to 51, wherein the critical current density of the sulfide-based ion-conducting structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting structure not having at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0259] 53. The solid electrolyte material of any one of items 37 to 52, wherein the critical current density of the sulfide-based ion-conducting structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is at least 10% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0260] 54. The solid electrolyte material of any one of items 37 to 53, wherein the critical current density of the sulfide-based ion-conducting structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is at least 20% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0261] 55. The solid electrolyte material of any one of items 37 to 54, wherein the critical current density of the sulfide-based ion-conducting structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is at least 30% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0262] 56. The solid electrolyte material of any one of items 37 to 55, wherein the critical current density of the sulfide-based ion-conducting structure having at least one of an excess amount of sulfur and an excess amount of lithium sulfide is at least 40% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting structure without at least one of an excess amount of sulfur and an excess amount of lithium sulfide.

[0263] 57. The critical current density of sulfide-based ion-conducting structures is 0.2 mA / cm 2 57. The solid electrolyte material of any one of items 37 to 56, wherein the solid electrolyte material is ultra-

[0264] 58. The critical current density of sulfide-based ion-conducting structures is 0.4 mA / cm 2 The solid electrolyte material of any one of items 37 to 57, which is ultra-

[0265] 59. The critical current density of sulfide-based ion-conducting structures is 0.6 mA / cm 2 59. The solid electrolyte material of any one of items 37 to 58, which is ultra-

[0266] 60. The critical current density of sulfide-based ion-conducting structures is 0.8 mA / cm 2 60. The solid electrolyte material of any one of items 37 to 59, which is ultra-

[0267] 61. The critical current density of sulfide-based ion-conducting structures is 1.0 mA / cm 2 61. The solid electrolyte material of any one of items 37 to 60, which is ultra-

[0268] 62. The critical current density of sulfide-based ion-conducting structures is 2.0 mA / cm 2 The solid electrolyte material of any one of items 37 to 61, which is ultra-

[0269] 63. The critical current density of sulfide-based ion-conducting structures is 3.0 mA / cm 2 The solid electrolyte material of any one of items 37 to 62, which is ultra-

[0270] 64. The critical current density of sulfide-based ion-conducting structures is 4.0 mA / cm 2 The solid electrolyte material of any one of items 37 to 63, which is ultra-

[0271] 65. The critical current density of sulfide-based ion-conducting structures is 5.0 mA / cm 2 The solid electrolyte material of any one of items 37 to 64, which is ultra-

[0272] 66. The solid electrolyte material of any one of items 37 to 65, wherein the sulfide-based ion-conducting structure contains phosphorus.

[0273] 67. The solid electrolyte material of any one of items 37 to 66, wherein the sulfide-based ion-conducting structure has an argyrodite structure.

[0274] 68. The solid electrolyte material of item 67, wherein the argyrodite structure has two or more halogens.

[0275] 69. A sulfide-based ion-conducting argyrodite structure comprising lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; one or more halogens; and an excess amount of sulfur incorporated into the sulfide-based ion-conducting argyrodite structure. A solid electrolyte material comprising:

[0276] 70. A sulfide-based ion-conductive argyrodite structure has the general formula: Li 12-m-x M m+ Y (6-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = optionally O 2- , Se 2- , Te 2- or a combination thereof combined with S 2- ; X - = F - , Cl - , Br<� - , I - or a combination thereof; x is in the range 0 ≦ x ≦ 2; n is greater than 0), the solid electrolyte material of item 69.

[0277] 71. The solid electrolyte material of item <0002,362><00,02363> 72. A sulfide-based ion-conductive argyrodite structure has the general formula: Li<0001,355>M2 m+ Y (9-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = optionally O 2- , Se 2- , Te 2- or a combination thereof combined with S 2- ; X - = F - , Cl - , Br - , I<� -or a combination thereof; x ranges from 0 ≦ x ≦ 2; n is greater than 0), the solid electrolyte material of item 69.

[0279] 73. The solid electrolyte material of item 72, where n ranges from 0 < n ≦ 1.

[0280] 74. The solid electrolyte material of any one of items 69 to 73, where an excess amount of sulfur is disposed within the defects of the sulfide-based ion-conductive allodidite structure.

[0281] 75. The solid electrolyte material of any one of items 69 to 74, where an excess amount of sulfur is disposed in the interstices of the lattice of the sulfide-based ion-conductive allodidite structure.

[0282] 76. The solid electrolyte material of any one of items 69 to 75, where an excess amount of sulfur exists in the form of superlattice stacking defects within the sulfide-based ion-conductive allodidite structure.

[0283] 77. The solid electrolyte material of any one of items 69 to 76, where the electronic conductivity of the sulfide-based ion-conductive allodidite structure having an excess amount of sulfur is less than the electronic conductivity of the stoichiometric sulfide-based ion-conductive allodidite structure having no excess amount of sulfur.

[0284] 78. The solid electrolyte material of any one of items 69 to 77, where the electronic conductivity of the sulfide-based ion-conductive allodidite structure having an excess amount of sulfur is less than half of the electronic conductivity of the stoichiometric sulfide-based ion-conductive allodidite structure having no excess amount of sulfur.

[0285] 79. The solid electrolyte material of any one of items 69 to 78, where the electronic conductivity of the sulfide-based ion-conductive allodidite structure having an excess amount of sulfur is less than one-fourth of the electronic conductivity of the stoichiometric sulfide-based ion-conductive allodidite structure having no excess amount of sulfur.

[0286] 80. The solid electrolyte material of any one of items 69 to 79, wherein the electronic conductivity of the sulfide-based ionically conductive argyrodite structure having an excess amount of sulfur is approximately one-tenth of the electronic conductivity of a nominal stoichiometric sulfide-based ionically conductive argyrodite structure without an excess amount of sulfur.

[0287] 81. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is 10 -7 81. The solid electrolyte material of any one of items 69 to 80, having a resistivity of less than S / cm.

[0288] 82. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is 10 -8 82. The solid electrolyte material of any one of items 69 to 81, having a resistivity of less than S / cm.

[0289] 83. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is 10 -9 83. The solid electrolyte material of any one of items 69 to 82, having a resistivity of less than S / cm.

[0290] 84. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is -10 84. The solid electrolyte material of any one of items 69 to 83, having a resistivity of less than S / cm.

[0291] 85. The solid electrolyte material of any one of items 69 to 84, wherein the critical current density of a sulfide-based ion-conducting argyrodite structure having an excess amount of sulfur is higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure having no excess amount of sulfur.

[0292] 86. The solid electrolyte material of any one of items 69 to 85, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of sulfur is at least 10% higher than the critical current density of the nominal stoichiometric sulfide-based ion-conducting argyrodite structure having no excess amount of sulfur.

[0293] 87. The solid electrolyte material of any one of items 69 to 86, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of sulfur is at least 20% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure having no excess amount of sulfur.

[0294] 88. The solid electrolyte material of any one of items 69 to 87, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of sulfur is at least 30% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure having no excess amount of sulfur.

[0295] 89. The solid electrolyte material of any one of items 69 to 88, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of sulfur is at least 40% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure having no excess amount of sulfur.

[0296] 90. The critical current density of sulfide-based ion-conducting argyrodite structures is 0.2 mA / cm 2 The solid electrolyte material of any one of items 69 to 89, which is ultra-

[0297] 91. The critical current density of a sulfide-based ion-conducting argyrodite structure is 0.4 mA / cm 2 The solid electrolyte material of any one of items 69 to 90, which is ultra-

[0298] 92. The critical current density of sulfide-based ion-conducting argyrodite structures is 0.6 mA / cm 2 The solid electrolyte material of any one of items 69 to 91, which is ultra-

[0299] 93. The critical current density of sulfide-based ion-conducting argyrodite structures is 0.8 mA / cm 2 The solid electrolyte material of any one of items 69 to 92, which is ultra-

[0300] 94. The critical current density of a sulfide-based ion-conducting argyrodite structure is 1.0 mA / cm 2 The solid electrolyte material of any one of items 69 to 93, which is ultra-

[0301] 95. The critical current density of a sulfide-based ion-conducting argyrodite structure is 2.0 mA / cm 2 The solid electrolyte material of any one of items 69 to 94, which is ultra-

[0302] 96. The critical current density of a sulfide-based ion-conducting argyrodite structure is 3.0 mA / cm 2 The solid electrolyte material of any one of items 69 to 95, which is ultra-

[0303] 97. The critical current density of a sulfide-based ion-conducting argyrodite structure is 4.0 mA / cm 2 The solid electrolyte material of any one of items 69 to 96, which is ultra-

[0304] 98. The critical current density of a sulfide-based ion-conducting argyrodite structure is 5.0 mA / cm 2 The solid electrolyte material of any one of items 69 to 97, which is ultra-

[0305] 99. The solid electrolyte material of any one of items 69 to 98, wherein the sulfide-based ion-conducting argyrodite structure contains phosphorus.

[0306] 100. A solid electrolyte material according to item 99, wherein the argyrodite structure has two or more halogens.

[0307] 101. A sulfide-based ion-conducting argyrodite structure comprising lithium; sulfur, optionally in combination with oxygen, selenium, tellurium, or a combination thereof; one or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; one or more halogens; and an excess amount of sulfur incorporated into the sulfide-based ion-conducting argyrodite structure. A solid electrolyte material comprising

[0308] 102. A sulfide-based ion-conductive allodilite structure has the general formula: Li 12-m-x+2n M m+ Y (6-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = optionally O 2- , Se<00,01404>, Te 2- or S combined with a combination thereof 2- ; X - = F - , Cl - , Br - , I - or a combination thereof; x is in the range 0 ≦ x ≦ 2; n is greater than 0), the solid electrolyte material of item 101.

[0309] 103. The solid electrolyte material of item 102, where n is in the range 0 < n ≦ 20.

[0310] 104. A sulfide-based ion-conductive allodilite structure has the general formula: Li 18-2m-x+2n M2 m+ Y (9-x)+n X x (where M m+ = B 3+ , Ga 3+ , Sb 3+ , Si 4+ , Ge 4+ , Sn 4+ , P 5+ , As 5+ or a combination thereof; Y = optionally O 2- , Se 2- , Te 2- or S combined with a combination thereof 2- ; X - = F -, Cl - , Br - , I - or a combination thereof; x is in the range of 0 ≦ x ≦ 2; n is greater than 0), the solid electrolyte material of item 101.

[0311] 105. The solid electrolyte material of item 104, where n is in the range of 0 < n ≦ 20.

[0312] 106. The solid electrolyte material of any one of items 101 - 105, where an excess amount of lithium sulfide exists in the form of a lithium sulfide layer within a sulfide-based ion-conductive argyrodite structure.

[0313] 107. The solid electrolyte material of any one of items 101 - 106, where an excess amount of lithium sulfide exists in the form of a superlattice stacking defect of multiple lithium sulfide layers within a sulfide-based ion-conductive argyrodite structure.

[0314] 108. The solid electrolyte material of any one of items 101 - 107, where the electronic conductivity of a sulfide-based ion-conductive argyrodite structure having an excess amount of lithium sulfide is less than the electronic conductivity of a stoichiometric sulfide-based ion-conductive argyrodite structure having no excess amount of lithium sulfide.

[0315] 109. The solid electrolyte material of any one of items 101 - 108, where the electronic conductivity of a sulfide-based ion-conductive argyrodite structure having an excess amount of lithium sulfide is less than half of the electronic conductivity of a stoichiometric sulfide-based ion-conductive argyrodite structure having no excess amount of lithium sulfide.

[0316] 110. The solid electrolyte material of any one of items 101 - 109, where the electronic conductivity of a sulfide-based ion-conductive argyrodite structure having an excess amount of lithium sulfide is less than one-fourth of the electronic conductivity of a stoichiometric sulfide-based ion-conductive argyrodite structure having no excess amount of lithium sulfide.

[0317] 111. The solid electrolyte material of any one of items 101 to 110, wherein the electronic conductivity of a sulfide-based ionically conductive argyrodite structure having an excess of lithium sulfide is approximately one-tenth of the electronic conductivity of a nominal stoichiometric sulfide-based ionically conductive argyrodite structure without an excess of lithium sulfide.

[0318] 112. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is -7 112. The solid electrolyte material of any one of items 101 to 111, having a resistivity of less than S / cm.

[0319] 113. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is 10 -8 113. The solid electrolyte material of any one of items 101 to 112, having a resistivity of less than S / cm.

[0320] 114. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is 10 -9 114. The solid electrolyte material of any one of items 101 to 113, having a resistivity of less than S / cm.

[0321] 115. The electronic conductivity of sulfide-based ionically conductive argyrodite structures is 10 -10 115. The solid electrolyte material of any one of items 101 to 114, having a resistivity of less than S / cm.

[0322] 116. The solid electrolyte material of any one of items 101 to 115, wherein the critical current density of a sulfide-based ion-conducting argyrodite structure having an excess amount of lithium sulfide is higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure without an excess amount of lithium sulfide.

[0323] 117. The solid electrolyte material of any one of items 101 to 116, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of lithium sulfide is at least 10% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure without an excess amount of lithium sulfide.

[0324] 118. The solid electrolyte material of any one of items 101 to 117, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of lithium sulfide is at least 20% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure without an excess amount of lithium sulfide.

[0325] 119. The solid electrolyte material of any one of items 101 to 118, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of lithium sulfide is at least 30% higher than the critical current density of a nominal stoichiometric sulfide-based ion-conducting argyrodite structure without an excess amount of lithium sulfide.

[0326] 120. The solid electrolyte material of any one of items 101 to 119, wherein the critical current density of the sulfide-based ion-conducting argyrodite structure having an excess amount of lithium sulfide is at least 40% higher than the critical current density of the nominal stoichiometric sulfide-based ion-conducting argyrodite structure without an excess amount of lithium sulfide.

[0327] 121. The critical current density of sulfide-based ion-conducting argyrodite structures is 0.2 mA / cm 2 The solid electrolyte material of any one of items 101 to 120, which is ultra-

[0328] 122. The critical current density of a sulfide-based ion-conducting argyrodite structure is 0.4 mA / cm 2 The solid electrolyte material of any one of items 101 to 121, which is ultra-

[0329] 123. The critical current density of sulfide-based ion-conducting argyrodite structures is 0.6 mA / cm 2 The solid electrolyte material of any one of items 101 to 122, which is ultra-

[0330] 124. The critical current density of sulfide-based ion-conducting argyrodite structures is 0.8 mA / cm 2 The solid electrolyte material of any one of items 101 to 123, which is ultra-

[0331] 125. The critical current density of sulfide-based ion-conducting argyrodite structures is 1.0 mA / cm 2 The solid electrolyte material of any one of items 101 to 124, which is ultra-

[0332] 126. The critical current density of sulfide-based ion-conducting argyrodite structures is 2.0 mA / cm 2 The solid electrolyte material of any one of items 101 to 125, which is ultra-

[0333] 127. The critical current density of a sulfide-based ion-conducting argyrodite structure is 3.0 mA / cm 2 The solid electrolyte material of any one of items 101 to 126, which is ultra-

[0334] 128. The critical current density of a sulfide-based ion-conducting argyrodite structure is 4.0 mA / cm 2 The solid electrolyte material of any one of items 101 to 127, which is ultra-

[0335] 129. The critical current density of a sulfide-based ion-conducting argyrodite structure is 5.0 mA / cm 2 The solid electrolyte material of any one of items 101 to 128, which is ultra-

[0336] 130. The solid electrolyte material of any one of items 101 to 129, wherein the sulfide-based ion-conducting argyrodite structure contains phosphorus.

[0337] 131. The solid electrolyte material of any one of items 101 to 130, wherein the sulfide-based ion-conducting argyrodite structure contains two or more halogens.

[0338] While various embodiments of the solid electrolyte material of the present disclosure have been shown and described, modifications will occur to those skilled in the art upon reading this specification, and the present application includes such modifications and is limited only by the scope of the claims. [Explanation of symbols]

[0339] 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28 unit cells 30 Solid electrolyte layer 32 Composite cathode layer 34 Positive current collector 36 Composite Anode Layer 38 Negative current collector 40 Lithium metal anode layer

Claims

1. One or more of lithium, sodium, aluminum, magnesium, iron and potassium; One or more of sulfur, oxygen, selenium and tellurium; One or more of boron, gallium, antimony, silicon, germanium, tin, phosphorus, and arsenic; and At least one of an excess of chalcogen and an excess of chalcogenide present in the form of superlattice stacking faults within a chalcogenide-based ion-conducting structure. Chalcogenide-based ion-conducting structures including A solid electrolyte material comprising:

2. 10. The solid electrolyte material of claim 1, wherein the excess chalcogen is present in the form of superlattice stacking faults within the chalcogenide-based ion-conducting structure.

3. A solid electrolyte material as described in claim 2, wherein the excess chalcogen comprises an excess amount of sulfur.

4. 10. The solid electrolyte material of claim 1, wherein the excess chalcogenide is present in the form of superlattice stacking faults within the chalcogenide-based ion-conducting structure.

5. 5. The solid electrolyte material of claim 4, wherein the chalcogenide-based ion-conducting structure has a visible (111) peak in the x-ray diffraction pattern corresponding to an excess of chalcogenide.

6. A solid electrolyte material as described in claim 4 or 5, wherein the excess chalcogenide includes an excess of lithium sulfide.

7. 7. The solid electrolyte material of claim 1, wherein the electronic conductivity of a chalcogenide-based ionically conductive structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is less than the electronic conductivity of a nominal stoichiometric chalcogenide-based ionically conductive structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

8. 7. The solid electrolyte material of claim 1, wherein the electronic conductivity of a chalcogenide-based ion-conducting structure having at least one of an excess of chalcogen and an excess of chalcogenide is less than half the electronic conductivity of a nominal stoichiometric chalcogenide-based ion-conducting structure not having at least one of an excess of chalcogen and an excess of chalcogenide.

9. The electronic conductivity of chalcogenide-based ionic conductive structures is 10 -7 The solid electrolyte material according to claim 1 , wherein the solid electrolyte material has a viscosity of less than 1.0 S / cm.

10. The electronic conductivity of chalcogenide-based ionic conductive structures is 10 -8 The solid electrolyte material according to claim 1 , wherein the solid electrolyte material has a viscosity of less than 1.0 S / cm.

11. A solid electrolyte material described in any one of claims 1 to 10, wherein the critical current density of a chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

12. 11. The solid electrolyte material of claim 1, wherein the critical current density of a chalcogenide-based ion-conducting structure having at least one of an excess amount of chalcogen and an excess amount of chalcogenide is at least 10% higher than the critical current density of a nominal stoichiometric chalcogenide-based ion-conducting structure not having at least one of an excess amount of chalcogen and an excess amount of chalcogenide.

13. The critical current density of chalcogenide-based ion-conducting structures is 0.2 mA / cm 2 The solid electrolyte material according to claim 1 , wherein the solid electrolyte material is greater than 100%.

14. The critical current density of chalcogenide-based ion-conducting structures is 0.4 mA / cm 2 The solid electrolyte material according to claim 1 , wherein the solid electrolyte material is greater than 100%.

15. 15. The solid electrolyte material of claim 1 , wherein the chalcogenide-based ion-conducting structure comprises lithium.